Lipid Nanoparticles Based Drug Delivery Systems: Design Innovations, Therapeutic Applications, and Translational Progress - Abdul Shadab; Md. Faheem Haider; Mohammad Abohassan (Journal of Pharmaceutical Innovation, 2027)

Phytochemical Profiling and Antibacterial Potential of Propolis Extract and Green Synthesis of Silver Nanoparticles: An Experimental and Computational Approach - Ateeq Ur Rahman; Mohammad Attaullah; Aqsa Gul; Robi Bibi; Bashir Ahmad; Aziz Ullah; Abdulwahed Fahad Alrefaei; Faheem Anwar; Sajid Ali (Journal of Pharmaceutical Innovation, 2027)

Ethosomal nanocarriers for enhanced skin drug delivery: a comprehensive review - Daniyal Khan; Md. Faheem Haider; Mohammad Abohassan (Molecular Biology Reports, 2026)

ASAP1 as a novel dual-level biomarker for tuberculosis: integrated genetic and proteomic evidence for early detection and disease monitoring - Faheem Shahzad; Shah Jahan; Ahsan Waheed Rathore; Fasihat ul Ain; Atia Ali; Mohammad Kashif; Ali Ammar; Romeeza Tahir; Nadeem Afzal (Molecular Biology Reports, 2026)

Dynamic response of unsaturated porous media subjected to buried moving strip loads - Guocai Wang; Siyu Jin; Shiwei Zhu; Syed Muhammad Faheem Rizvi (Soil Dynamics and Earthquake Engineering, 2026)

Zygote electroporation of base editor ribonucleoproteins enables efficient single-target editing but reveals limitations of multiplex base editing in sheep - Mengting Cheng; Yun Wang; Haoran Xu; Muhammad Faheem Qurashi; Xinrong Li; Xueyi Ding; Jun Liu; Wenhui Pi; Chunhe Xiang (Theriogenology, 2026)

A sustainable mechanical engineering framework for biomaterials in healthcare system development - Helal Uddin; Laraib Zanib; Izzah Atif; Basmalaa Ahmed Thabet; Zaryab Basharat; Muhammad Haris Malik; Faheem Ahmad (Next Research, 2026)

Performance prediction of multi-effect desalination (MED) plant: Experimental evaluation, machine learning modelling and optimization - Uzair Ahmad; Muhammad Ahmad Jamil; Muhammad Wakil Shahzad; Faheem Hassan Akhtar (Desalination, 2026)

The speed–precision paradox in seeding technology: a system-level review of regime transitions, validation gaps, and energy trade-offs - Saddam Hussain; Zhaoyu Rui; Junyan He; Zhao Zhang; Mustafa Mhamed; Muhammad Faheem; Seyed Mohamad Javidan; Muhammad Usman Farid; Alaa Saeed; Mahmoud A. Abdelhamid (Computers and Electronics in Agriculture, 2026)

Nano-microbial suppression of Tribolium castaneum: Mortality, repellency, and enzyme responses to ginger-derived iron oxide nanoparticles and PGPR strains - Aneela Shaheen; Zeeshan Ahmad; Tauqeer Ahmed Qadri; Sidra Batool; Faheem Ahmad; Muhammad Nadeem Hassan; Humaira Yasmin (Journal of Stored Products Research, 2026)

Carbon source-driven anaerobic assimilation of dye-derived dissolved organic nitrogen: A low-carbon strategy with performance and mechanism insights - Xumeng Lin; Huahan Huang; Ying Wu; Ling Xiong; Yang Meng; Faheem Ahmed Ghori; He Cui; Yinchuan Yang; Hong Chen; Gang Xue (Environmental Research, 2026)

Techno-economic assessment of batch reverse osmosis desalination systems: Rating and design - Qais N. Al-Oweiti; Omar G. Kaoud; M.A.M. Ahmed; Faheem Ejaz; Muhammad H. Elbassoussi; Syed M. Zubair (Desalination, 2026)

Genomic prediction of silage traits in maize hybrids using additive, dominance, and epistatic models - Gönül Cömertpay; Nergiz Çoban; İbrahim Cerit; İskender Onaç; Faheem Shehzad Baloch; Rüştü Hatipoğlu; Alper Adak (Euphytica, 2026)

Nano-enabled spray-induced RNA interference against fungal pathogens of oilseed crops: carrier performance, delivery evidence and field translation - Amjad Ali; Sana Hanif; Afifa Azad; Kanza Azad; Tehreem Eraf; Muhammad Aasim; Ashrit Gulfraz; Faheem Shehzad Baloch; Muhammad Shahbaz (World Journal of Microbiology and Biotechnology, 2026)

Long-Term Fermented Chicken Manure (CM) Amendment Enhances Soil Health, Sugar Beet Yield, and Shifts Microbial Functional Diversity - Jianyu Zhang; Songlin Yang; Xiaochen Lin; Shafaque Sehar; Muhammad Ishfaq; Muhammad Riaz; Muhammad Faheem Adil; Saqib Bilal; Xiaoyu Zhao; Jean Wan Hong Yong; Baiquan Song (Sugar Tech, 2026)

Seismic segmentation and slab dehydration beneath Java, Indonesia: Geodynamic and hazard implications - Fitriani Fitriani; Yingfeng Ji; Jun Yang; Haris Faheem; Waqar Ahmed; Ye Zhu; Shoichi Yoshioka; Nobuaki Suenaga (Journal of Asian Earth Sciences, 2026)

Harnessing biostimulants to alleviate potentially toxic element stress in vegetable crops - Amna Jamil; Waqas Liaqat; Asia Maqbool; Pramod Sargar; Muhammad Anwar-Ul-Haq; Shraddha Samindre; Muhammad Faheem Jan; Faheem Shehzad Baloch; Heba I. Mohamed; Muhammad Tanveer Altaf (Planta, 2026)

Nano-enabled RNAi strategies for sustainable citrus protection against viral pathogens - Amjad Ali; Ameel Riaz; Muhammad Faiq; Jaya Seelan Sathiya Seelan; Faheem Shehzad Baloch; Muhammad Aasim; Muhammad Shahbaz (Planta, 2026)

Multi-trait plant growth-promoting endophytic fusarium proliferatum from phoenix dactylifera enhanced wheat growth under drought stress condition - Salman Khan; Khalil Ur Rahman; Nida Karishma; Mamoona Rauf; Humaira Gul; Muhammad Hamayun; Abdulwahed Fahad Alrefaei; Faheem Anwar; Sajid Ali; Muhammad Arif (Acta Physiologiae Plantarum, 2026)

Bile acids in Alzheimer’s disease: a double-edged sword in gut–liver–brain signaling and neurodegeneration - Rehana Basri; Hayder M. Al-kuraishy; Mubarak Alruwaili; Ali I. Al-Gareeb; Ali K. Albuhadily; Athanasios Alexiou; Marios Papadakis; Safaa A. Faheem; Gaber El-Saber Batiha (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Alzheimer’s disease (AD) is a progressive neurodegenerative disorder characterized by amyloid-β (Aβ) deposition, tau pathology, synaptic dysfunction, neuroinflammation, and metabolic impairment. Increasing evidence suggests that bile acids, traditionally recognized for their roles in lipid digestion and hepatic metabolism, act as endocrine signaling molecules that influence central nervous system (CNS) homeostasis. Through enterohepatic circulation and microbiota-dependent biotransformation, bile acid composition is dynamically regulated and can modulate peripheral metabolic and immune pathways with downstream effects on the brain. Notably, bile acid signaling via key receptors such as the farnesoid X receptor (FXR) and the Takeda G protein-coupled receptor 5 and G-protein-coupled bile acid receptor 1 (TGR5/GPBAR1) has emerged as a mechanistic bridge linking liver–gut physiology to neuroinflammatory and neurodegenerative processes. Altered bile acid profiles have been reported in AD and mild cognitive impairment, with accumulating findings suggesting that hydrophobic secondary bile acids may contribute to blood–brain barrier (BBB) disruption and neurotoxicity. In contrast, hydrophilic bile acids may exert neuroprotective and anti-inflammatory effects. In addition, bile acids drive the release of gut hormones such as glucagon-like peptide 1 (GLP-1) and fibroblast growth factor 19 (FGF19), highlighting indirect neurometabolic pathways relevant to cognition and neurodegeneration. This narrative review synthesizes current biochemical, experimental, and clinical evidence supporting a role for bile acid signaling in AD pathogenesis and progression. We discuss receptor-mediated pathways, microbiota-bile acid interactions, neuroimmune modulation, and translational perspectives, proposing that bile acid–based biomarkers and therapeutic strategies targeting FXR/TGR5 signaling may represent promising avenues for future AD intervention.

Lipid-based nanocarrier-enabled combination therapy for breast cancer: overcoming drug resistance toward precision oncology - Abdul Shadab; Md. Faheem Haider; Mohammad Abohassan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Elicitors in Plant Defense: Exploring Their Role in Biotic and Abiotic Stress Resistance - Muhammad Tanveer Altaf; Waqas Liaqat; Muhammad Aneeq Ur Rahman; Chidera Anuforo; Asia Maqbool; Amjad Ali; Muhammad Faheem Jan; Muhammad aasim; Heba I. Mohamed; Faheem Shehzad Baloch (Journal of Plant Growth Regulation, 2026)

Biogas upgrading technologies with emphasis on membrane separation performance - Junaid Ahmad; Rizwan Nasir; Muhammad Faheem; Mustafa Alsaady; Khuram Maqsood; Chawalit Ngamcharussrivichai (Biomass and Bioenergy, 2026)

Advancements in Wheat Rust Resistance through Molecular and Field-Based Approaches - Muhammad Waheed Riaz; Dehua Wang; Shams ur Rehman; Yufeng Zhang; Faheem Tariq; Alam Sher; Shabbir Hussain; Muhammad Aamir Manzoor; Abdul Raziq; Zhiying Deng (Journal of Soil Science and Plant Nutrition, 2026)

Genetic Diversity and Population Structure of 72 Turkish Ficus carica (L.) Genotypes Assessed Using SCoT Markers - Meliha Feryal Sarıkaya; Muhammad Azhar Nadeem; Sarmad Ali Qureshi; Mehmet Bedir; Muhammed Tatar; Amjad Ali; Muhammad Tanveer Altaf; Viyan Acar Uçer; Kağan Kökten; Erdal Aglar; Faheem Shehzad Baloch (Biochemical Genetics, 2026)

Correction: Gut microbiota profile, potential engineering techniques and its genetic and epigenetic implications in poultry health - Nuruliarizki Shinta Pandupuspitasari; Sugiharto Sugiharto; Faheem Ahmed Khan; Muhammad Asif Raza; Dela Ayu Lestari; Asep Setiaji; Ikania Agusetyaningsih (World Journal of Microbiology and Biotechnology, 2026)

Vibration mitigation for underground tunnels using jet-grouted barriers subjected to impact pile driving - Syed Muhammad Faheem Rizvi; Guocai Wang; Juntao Wu (Tunnelling and Underground Space Technology, 2026)

Two-dimensional WS2/fluorinated g-C3N4 microcomposite for enzyme-free electrochemical detection of acetaminophen - Thangavelu Kokulnathan; Selvaganapathy Ganesan; Tzyy-Jiann Wang; Arunkumar Palaniappan; Thamraa Alshahrani; Faheem Ahmed (Journal of Environmental Chemical Engineering, 2026)

Two-stage A/O process decontaminates urea and total nitrogen in textile printing wastewater: Focus on combined Na2SO4 and Na2S2O4 salinity - Faheem Ahmed Ghori; Xumeng Lin; Ying Wu; Yimei Cheng; Ling Xiong; Hong Chen; Muhammad Usman Ghani; Gang Xue (Bioresource Technology, 2026)

Synthesis of Novel Bentonite Composites for Enhanced Remediation of Basic Fuchsin Dye - Ayesha Naseer; Ruba Munir; Gadah Albasher; Muhammad Husnain Manzoor; Murtaza Sayed; Faheem Abbas; Saima Noreen (Water, Air, & Soil Pollution, 2026)

Nanoparticles in Vegetable Production: From Soil to Human Health - Amna Jamil; Muhammad Tanveer Altaf; Ishtiaq Ahmad; Waqas Liaqat; Asia Maqbool; Muhammad Anwar-Ul-Haq; Pramod Sargar; Heba I. Mohamed; Faheem Shehzad Baloch (Water, Air, & Soil Pollution, 2026)

Impact Assessment of Pre-Isolated Iron-Solubilizing Rhizobacteria and Auxin on Iron Content and Growth of Potato - Faheem Waris; Ayesha Iqbal; Khairiah Mubarak Alwutayd; Ahad Mohammed Althyab; Hanan M. Alharbi (Potato Research, 2026)

Targeting of MAPK–ERK1/2 signaling by metformin in asthma: an updated mechanistic insight - Manal Ewaiss Hassan; Hayder M. Al-kuraishy; Athanasios Alexiou; Marios Papadakis; Safaa A. Faheem; Eman K. Rashwan; Gaber El-Saber Batiha (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Asthma is a heterogeneous chronic inflammatory airway disease characterized by persistent inflammation, dysregulated immune signaling, and progressive airway remodeling. It has been shown that asthma pathogenesis involves multiple signaling pathways. It has been illustrated that the mitogen-activated protein kinase/extracellular signal-regulated kinase 1/2 (MAPK/ERK1/2) cascade, which emerges as a central regulator linking immune activation, epithelial dysfunction, and structural remodeling of the airway, is implicated in the pathogenesis of asthma. Sustained ERK1/2 activation is consistently demonstrated in human asthmatic airways and experimental models, correlating with disease severity, inflammatory cell infiltration, and corticosteroid resistance. This review provides a comprehensive and critical discussion of the ERK1/2 signaling in asthma, spanning immune cells, airway epithelium, and airway smooth muscle. We evaluate preclinical and translational evidence supporting ERK1/2 as a therapeutic target and examine emerging pharmacological strategies, including indirect pathway modulation via AMP-activated protein kinase (AMPK) activation and drug repositioning with the anti-diabetic metformin. By integrating mechanistic insights with therapeutic implications, this review positions ERK1/2 as a pivotal signaling node for precision targeting in severe, treatment-refractory asthma.

Mitigation of Root-Knot Nematode (Meloidogyne incognita) in Beta Vulgaris Through Biologically Synthesized Chitosan-Copper Nanoparticles (CS-Cu NPs) - Mohammad Shariq; Faryad Khan; Mohammad Haris; Taruba Ansari; Faheem Ahmad; Mansoor Ahmad Siddiqui (Journal of Soil Science and Plant Nutrition, 2026)

Development and Optimization of a Fixed Dose Combination Tablet Containing Ibuprofen and Loratadine Using Design Expert and Box-Behnken Design - Muhammad Faheem; Lateef Ahmad; Umar Farooq; Kiramat Ali Shah; Ismail Khan; Abdur Rauf; Omar S. Bahattab; Yahya S. Al-Awthan; Anees Ahmed Khalil; Huda Ateeq (Journal of Pharmaceutical Innovation, 2026)

Feasibility of home-based, remotely delivered exercise training to improve physical function in older sepsis survivors: a pilot randomized controlled trial - Yi Lin; Rola S. Zeidan; Rezvan Ghaderpanah; Margaret K. Ohama; Min-Han Jung; Naveen Baskaran; Juan Sarmiento Delgado; Stephen D. Anton; Barbara K. Smith; Christiaan Leeuwenburgh; Fang-Chi Hsu; Philip A. Efron; et al. (GeroScience, 2026)
Sepsis survivors frequently experience post-discharge physical function decline and encounter logistical barriers to participation in traditional outpatient rehabilitation. This pilot study examined the feasibility, safety, and preliminary efficacy of a remotely delivered, home-based exercise program on physical function in older sepsis survivors. In this single-blinded, randomized controlled trial (RCT), sepsis survivors aged ≥ 55 years were randomized to (a) 12 weeks of avatar-guided, progressive exercise training group (EX) or (b) a standard care control group (CO). Primary outcomes were feasibility (retention, adherence) and safety (adverse events), whereas secondary outcomes were changes in the 30-s Sit-to-Stand (30SSTS), 4-Stage Balance Test (4SBT), Timed Up-and-Go (TUG) tests, and Eastern Cooperative Oncology Group/Zubrod's (ECOG/Zubrod) performance status score. Twenty-one participants were randomized to either EX ( n = 10, mean age = 69.6 ± 8.5 years, 40% females) or CO ( n = 11, mean age = 72.3 ± 7.9 years, 45% females). Mean retention was 95% and adherence to exercise training was 76%. Thirty-four adverse events (AEs) occurred (EX = 11; CO = 16; consented but not randomized = 7 events), including four serious AEs that were unrelated to the study. The EX group showed trends toward improvements in lower-extremity strength (30SSTS: 1.14 ± 2.91 repetitions, Cohen’s d = 0.393) and balance (4SBT: 5.07 ± 4.75 s, d = 1.07), whereas the CO group showed no change in balance on the 4SBT (0.01 ± 4.38 s, d = 0.003) and trends toward decline in lower-extremity strength on the 30SSTS (− 0.88 ± 0.99 repetitions, d = − 0.883). TUG performance showed modest trends toward reductions in completion time in both groups (EX: − 1.42 ± 6.58 s, d = − 0.216; CO: − 1.27 ± 2.73 s, d = − 0.466). ECOG/Zubrod scores showed a modest trend toward improvement in the EX group subset. This pilot RCT demonstrated that a 12-week, remotely delivered exercise program was safe and feasible for older sepsis survivors and showed preliminary signals of positive change in lower-extremity strength, balance, and functional status, which warrants testing efficacy in an adequately powered Phase IIb RCT. ClinicalTrials.gov NCT05568511.

An attempt at underwater image lightweight super-resolution using transformer and frequency-domain learning - Haoran Wu; Haitao Wang; Yifan Zhang; Muhammad Yasir Faheem; Xinghua Wang (Frontiers in Marine Science, 2026)
Lightweight image Super-resolution (SR) is a computer vision technology that aims to recover high-quality image details from low-resolution images with limited computing costs. While Transformer-based SR models have made remarkable advancements, their balanced edge-end deployment and reconstruction quality have been notably hindered by complex underwater imaging conditions and the scarcity of publicly available high-quality datasets. To address these issues, we propose a Frequency-domain Learning Transformer (FLT) for underwater images SR, which leverages complementary information from spatial and frequency domains to enable fine-grained detail reconstruction while reducing storage and computing costs. Specifically, FLT comprises Residual Dual-domain Joint Learning Transformer Blocks (RDTBs). Each RDTB captures low-frequency structures via the spatial-domain branch and high-frequency textures via the frequency-domain branch, thereby enhancing fine-grained details of lightweight SR. Furthermore, a Multi-scale FeedForward Neural (Ms-FFN) network is incorporated into each RDTB as an auxiliary detail enhancement module, which improves the visual fidelity of reconstructed images through multi-scale feature aggregation. We perform visual and quantitative comparisons, ablation studies, and model analyses against state-of-the-art methods on both the public UFO-120 dataset and the KLSG-II dataset. Experimental results demonstrate that FLT achieves performance comparable to or exceeding state-of-the-art SR models, while having significantly reduced by about 50% to 60% parameters and drastically reduced computational cost. This unique balance between reconstruction quality and efficiency underscores FLT’s superiority for lightweight underwater SR, providing a promising solution for resource-constrained underwater imaging applications. The code is available at https://github.com/WanghtCC/FLT .

Synthesis, radiolabelling and preliminary evaluation of [68Ga]Ga-DOTA-linked cyanuric chloride–glu-ureido scaffold for PSMA PET imaging - Mohd Faheem; Vaibhav Pandey; Anjali Pal; Pradeep Kumar Sharma; Manisha Prasad; Manish Dixit (Molecular Diversity, 2026)

Capacitive deionization of emerging oxyanions: Selective electrosorption, recovery strategies, and mechanistic insights - Muhammad Faheem; Jisha Kuttiani Ali; Fathima Arshad; Zubair Ahmad; Emad Alhseinat (Desalination, 2026)

Charcoal rot in sesame: infection biology, host resistance mechanism, and genomic-enabled strategies for durable resistance breeding - Amjad Ali; Muhammad Azhar Nadeem; Fatih Ölmez; Cemal Kurt; Faheem Shehzad Baloch (Theoretical and Applied Genetics, 2026)
Sesame ( Sesamum indicum L.) is a globally important oilseed crop, but its production is constrained by charcoal rot, caused by the soil-borne fungus Macrophomina phaseolina. The pathogen’s exceptionally broad host range, long-term soil persistence through microsclerotia, and increased aggressiveness under high temperature and drought make charcoal rot a major destructive constraint in sesame-growing regions. This review integrates current knowledge on the biology, epidemiology, infection processes, and genetic population variability of Macrophomina spp. in relation to charcoal rot development in sesame. We also summarize key host resistance mechanism including pathogen perception, cell wall reinforcement, phenylpropanoid-mediated defense, antioxidant responses, and associated physiological and molecular adaptations. Particular attention is given to the challenges of resistance screening under variable environmental conditions, including heat- and drought-associated disease expression and pathogen diversity, which complicate the identification of stable resistance sources. The review further examines progress in sesame improvement through germplasm characterization, mutation breeding, interspecific introgression, high-throughput phenotyping, and genomic-assisted approaches such as QTL mapping, genome-wide association studies (GWAS), marker-assisted selection, genomic selection, and functional validation. Integrating these tools with multi-omics and gene-editing strategies offers a promising route for accelerating the development of durable, climate-resilient charcoal rot resistance cultivars. Broader use of diverse germplasm, standardized multi-environment phenotyping, and international collaboration will be essential for sustainable resistance breeding and future sesame production.

Phosphodiesterase signaling in asthma: mechanistic insights and emerging therapeutic strategies - Abdulelah Alnusayri; Hayder M. Al-kuraishy; Athanasios Alexiou; Marios Papadakis; Safaa A. Faheem; Mubarak Alruwaili; Gaber El-Saber Batiha (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Asthma is a clinically and biologically heterogeneous disease for which current anti-inflammatory therapies, including inhaled corticosteroids, remain insufficient for many patients. Therefore, repurposing other FDA-approved drugs, such as phosphodiesterase (PDE) inhibitors, may be beneficial in the management of asthma. PDEs are central regulators of cyclic nucleotide signaling, modulating airway smooth-muscle tone, mucociliary function, and immune-cell activity by compartmentalizing the control of cAMP and cGMP. Although PDE4 inhibitors have shown strong pre-clinical efficacy, their translation into clinical practice has been hindered by dose-limiting systemic toxicities, revealing a persistent gap between mechanistic promise and therapeutic utility. This review synthesizes emerging insights into PDE isoenzyme selectivity, spatial localization, and cross-regulatory interactions across structural and immunocompetent airway cells. We outline how isoform- and splice-variant–specific functions contribute to key asthmatic phenotypes and evaluate innovative therapeutic strategies, including dual PDE3/4 inhibition, inhaled delivery approaches, and next-generation selective modulators designed to overcome historical limitations. By integrating these advances within an endotype-driven precision-medicine framework, this review provides a path toward unlocking the full therapeutic potential of PDE-targeted interventions in asthma.

Liposome-Based Drug Delivery Systems: Mechanisms, Preparation Strategies, Clinical Status, and Therapeutic Applications - Abdul Shadab; Md. Faheem Haider; Mohammad Abohassan (AAPS PharmSciTech, 2026)

Identification of Polo-like kinase-1 (PLK-1) inhibitors from Centella asiatica (Gotu Kola) using UHPLC and in-silico approaches - Kajim Ali; Mohsin Ali Khan; Waseem Ahmad Ansari; Priyanka Maurya; Hasan Aslam; Sudhir Kumar; Mohammad Faheem Khan (Natural Product Research, 2026)

Isolation, characterization, quantification and antioxidant activity of compounds from Myrica esculenta - Jyoti Kundal; Amit Ranjan Pandey; Waseem Ahmad Ansari; Fahmina Rizvi; Kajim Ali; Mohd Aamish Khan; Mohd Baqar Ali; Devendra Pratap Mishra; Mohammad Faheem Khan (Natural Product Research, 2026)

SIRT1 Activators as Geroprotective Agents in Brain Aging: Mechanisms and Therapeutic Potential - Ayman Ali Mohammed Alameen; Hayder M. Al-Kuraishy; Ali I. Al-Gareeb; Athanasios Alexiou; Marios Papadakis; Safaa A. Faheem; Gaber El-Saber Batiha (NeuroMolecular Medicine, 2026)
The brain undergoes profound molecular and structural changes during the aging process, resulting in the development of neurodegeneration, cognitive impairment, and increased vulnerability to chronic diseases. At the cellular level, brain aging is characterized by oxidative damage, genomic instability, and chronic low-grade inflammation known as inflammaging. Central to this process is Sirtuin 1 (SIRT1), a NAD + -dependent class III histone deacetylase, known for its regulatory role in chromatin remodeling, oxidative stress responses, mitochondrial biogenesis, and neuroplasticity. Recent research has identified SIRT1 as a molecular target capable of reversing or attenuating several hallmarks of aging, particularly within the central nervous system (CNS). This narrative review critically evaluates the emerging evidence surrounding the geroprotective effects of SIRT1 activators, which exert dual actions, senomorphic and senolytic, via modulation of signaling pathways, thereby reducing neuronal senescence, enhancing autophagy, and mitigating inflammatory responses. The discussion also addresses the region-specific role of SIRT1 across the brain, particularly in the hippocampus and hypothalamus, which are essential for memory, energy homeostasis, and resilience to stress. Additionally, this review explores how SIRT1 depletion during aging contributes to the development of synaptic dysfunction, impaired cognitive function, and susceptibility to neurodegenerative diseases such as Alzheimer’s disease (AD) and Parkinson’s disease (PD). The therapeutic potential of SIRT1 activators is supported by preclinical and early clinical studies, suggesting their value in preventing or delaying brain aging. Thus, SIRT1 could be a promising pharmacological target for age-associated brain disorders, warranting more robust translational studies to validate these findings in humans.

Advancing diagnostic biomarkers in Alzheimer’s disease: interdisciplinary innovations and technological frontiers - Faheem Patwekar; Mohsina Patwekar; Lee Seong wei; Rohit Sharma; Ryan Varghese; Arifullah Mohammed (Human Cell, 2026)

Naphthalene-anchored ETTA-based 2D-covalent organic frameworks exhibiting restricted intramolecular rotation for fluorescence sensing of nitroaromatic compounds - Muhammad Faheem; Toheed Akhter; Yongyue Ding; Yuyang Tian; Zhiheng Gao; Kun Wang; Lingliang Long (Journal of Environmental Chemical Engineering, 2026)

A comprehensive thermal-hydraulic assessment of offset strip fin flat-tube heat exchangers under humid conditions: Numerical and artificial neural network approaches - Faheem Ejaz; Shahzada Zaman Shuja; Naef A.A. Qasem; Syed M. Zubair (International Journal of Refrigeration, 2026)

Environmental friendly synthesis of cobalt-doped maghemite (Co-γ-Fe2O3) photocatalysts for visible-light driven wastewater treatment - T. Iqbal; M. Faheem; A. Almohammedi; M. Ijaz (International Journal of Environmental Science and Technology, 2026)

Determining the cutting wastage and risk factors involved in the manufacturing of denim trousers – a step towards sustainable apparel industry - Abher Rasheed; Salman A. Cheema; Nadeem Nasir; Abdu R. Rahman; Faheem Ahmad; Sheraz Ahmad (Environment, Development and Sustainability, 2026)

Pharmacological investigation of natural compounds for therapeutic potential in neuropathic pain - Muhammad Faheem; Arif-ullah Khan; Fawad Ali Shah (Natural Product Research, 2026)

YOLOv8n-PFA: a parallel fusion attention network for enhanced target detection in challenging environments - Muhammad Rashid; Junfeng Wang; Faheem Ahmed; Naeem Ahmed; Syed Agha Hassnain Mohsan; Eatedal Alabdulkreem; Samih M. Mostafa (Frontiers in Marine Science, 2026)
Introduction Underwater target detection plays a crucial role in marine environmental monitoring and ocean exploration. However, accurate detection remains challenging due to low illumination, blurred small objects, and complex background interference. Although convolutional neural network-based detectors have improved detection performance, many existing approaches are computationally expensive, limiting their deployment on resource-constrained underwater platforms. Methods To address these challenges, we propose YOLOv8n-PFA, a lightweight and high-precision underwater object detection framework. The proposed method introduces a novel Parallel Fusion Attention (PFA) module that models channel and spatial attention in parallel using residual connections to enhance discriminative features while suppressing background noise. The Wise Intersection over Union (WIoUv3) loss is incorporated to stabilize training and improve localization accuracy. Additionally, depth-wise convolutions (DWConv) are strategically applied to reduce model parameters and computational complexity. To further validate generalization capability, the PFA module is also integrated into YOLOv11n. Results Experimental results show that YOLOv8n-PFA achieves 84.2% mean Average Precision (mAP) on the URPC2020 dataset with 2.68 M parameters and 7.7 GFLOPs, and 84.8% mAP on the RUOD dataset with 2.98 M parameters and 7.9 GFLOPs. When integrated into YOLOv11n, the model achieves 84.7% mAP on URPC2020 and 85.3% on RUOD with only 2.76 M parameters and 6.5 GFLOPs. Across both datasets, the proposed approach improves mAP by 2.8-4.1% over baseline models while maintaining a lightweight architecture. Discussion The results demonstrate that the proposed framework provides an effective and computationally efficient solution for real-time underwater target detection in challenging marine environments. The consistent performance gains across different YOLO generations further confirm the scalability and robustness of the proposed PFA module.

Integrative regulatory networks modulating arbuscular mycorrhizal symbiosis - Yaseen Khan; Sulaiman Shah; Muhammad Faheem Jan; Mohammed Bouskout (Rhizosphere, 2026)

Surface-modified ZnSe nanoparticles for removal of cadmium (Cd2+) ions from water - Khurshed A. Shah; Faheem A Shiekh; Humaira S. Wani; S.M.A. Andrabi; Prabhakar Misra (Next Research, 2026)

Evaluating Azolla pinnata for Nutrient and Organic Pollutant Removal from Sugar Mill Wastewater: A Mathematical Modeling Approach - Jogendra Singh; Faheem Ahamad; Upasna Sharma; Vinod Kumar (Water, Air, & Soil Pollution, 2026)

Praziquantel ameliorates leflunomide-induced nephrotoxicity in mice: a novel therapeutic approach targeting TGF-β/Smad/Wnt/β-catenin/NF-κB/PPAR-γ signaling and Nrf-2 - Weam A. Elkady; Safaa A. Faheem; Reem M. Hazem; Naglaa F. El-Orabi (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Leflunomide (LF), an essential immunomodulator for autoimmune disorders, poses a risk of nephrotoxicity. This work was designed to examine the possible mechanisms of LF nephrotoxicity and to investigate the potential protective role of praziquantel (PZQ), an anti-helminthic drug, against LF-induced nephrotoxicity in mice. Forty male albino mice were randomly allocated into four groups. Group one acted as the control. Group two received LF at (10 mg/kg, P.O.). The third group was given both LF (10 mg/kg, P.O.) and PZQ (300 mg/kg, P.O.). Finally, the fourth group was given PZQ (300 mg/kg, P.O.). After eight weeks, the mice were euthanized following anesthesia, and their kidneys were extracted for biochemical and histopathological analysis. Leflunomide (LF) significantly increased serum creatinine (0.88 ± 0.01 mg/dL vs. 0.16 ± 0.01 mg/dL, p < 0.05) and BUN levels (69.15 ± 3.73 mg/dL vs. 32.52 ± 1.18 mg/dL, p < 0.05), while reducing albumin levels by 27.26%. Co-treatment with praziquantel (PZQ) markedly restored renal function, decreasing creatinine and BUN by 71.6% and 34.2%, respectively ( p < 0.05), and increasing albumin by 1.2-fold. PZQ also significantly reduced oxidative stress markers (MDA 56.98%, p < 0.05) and pro-inflammatory cytokines (IL-6 − 73.69%, p < 0.05), while upregulating antioxidant (Nrf-2 + 6.7-fold) and anti-inflammatory (PPAR-γ + 3.1-fold) pathways. These statistically significant improvements confirm the nephroprotective efficacy of PZQ against LF-induced nephrotoxicity through modulation of TGF-β/Smad, Wnt/β-catenin, NF-κB, Nrf-2, and PPAR-γ signaling pathways.

A bibliometric review on nano-materials in bituminous binders and mixes: research trends and knowledge gaps - Towseef Ahmed Gilani; Faheem Sadiq Bhat; Mohammad Idrees Gilani; Mohamad Shafi Mir; Peerzada Danish; Jasir Mushtaq; Iftekar Gull; Asif Akbar (Innovative Infrastructure Solutions, 2026)

Efficient De Novo Assembly and Recovery of Microbial Genomes from Complex Metagenomes Using a Reduced Set of k-mers - Hajra Qayyum; Muhammad Faheem Raziq; Haseeb Manzoor; Syed Shujaat Ali Zaidi; Amjad Ali; Masood Ur Rehman Kayani (Interdisciplinary Sciences: Computational Life Sciences, 2026)

Agricultural and socio-ecological benefits of reducing chemical nitrogen fertilizer and using organic amendments: a sugar beet case study in China's black soil region - Yunlong Guo; Xiaochen Lin; Muhammad Faheem Adil; Muhammad Ishfaq; Muhammad Riaz; Shafaque Sehar; Songlin Yang; Yan Wang; Zhishan Yan; Baiquan Song (Applied Soil Ecology, 2026)

Exploring the therapeutic potential of Murraya koenigii: a comprehensive study on the neuroprotective effects against rotenone-induced Parkinson’s disease in mice - Rabia Anjum; Chand Raza; Mehwish Faheem (Advances in Traditional Medicine, 2026)

A surrogate for predicting heave added mass in cylindrical point absorbers using a sequential geometry-to-frequency regression framework - Faheem Ijaz; Masri Bin Baharom; Qasim Zeeshan (Ocean Engineering, 2026)

Interface synergistic-driven electronic modulation in amorphous CoFeB@g-C3N4 for high-performance bifunctional OER/HER electrocatalysis - Abdul Haq; Anuj Kumar; Muhammad Arif; Umair Azhar; Huma Ahmad; Unaiza Talib; Mahnoor Ahmed; Muhammad Asim Mushtaq; Muhammad Sagir; Muhammad Faheem Maqsood; Kumar Venkatesan; Ghulam Yasin (Journal of Environmental Chemical Engineering, 2026)

Antibacterial Activity of Anthraquinones Isolated from Reynoutria Japonica Against Staphylococcus aureus: An in Silico and In Vitro Approach - Iqra Anam Khawaja; Sajid Ali; Muhammad Faheem; Syed Babar Jamal; Adnan Haider; Falak Niaz; Mi-Jeong Ahn; Mutiullah Khattak; Atif Ali Khan Khalil (Journal of Pharmaceutical Innovation, 2026)

Occurrence and Prevalence of Rice Root-knot Nematode (Meloidogyne graminicola) in Upper Gangetic Plain of India and Its Management - Ziaul Haque; Faheem Ahamad; Mohd Shahid Anwar Ansari; Mujeebur Rahman Khan (Journal of Crop Health, 2026)

Natural products as HMG-CoA reductase inhibitors (statins) for the management of non-communicable diseases - Radwa N. Muhammad; Nora M. Aborehab; Shaza H. Aly; Noha N. Nasr; Merhan O. Hindam; Aya M. Mustafa; Safaa A. Faheem; Mariam H. Fawzy; Mohammed E. Abo-El Fetoh; Ahmed M. El-Dessouki; Mostafa A. Rabie; Riham A. El-Shiekh; et al. (Inflammopharmacology, 2026)
Non-communicable diseases, such as diabetes, cancer, as well as cardiovascular, metabolic, and central nervous system disorders stand for significant global health burden. Statins, as HMG-CoA reductase inhibitors, have emerged as a basis in the management of hypercholesterolemia and the prevention of cardiovascular disorders. In this review, we summarize the role of statins in a variety of pathologies, ranging from their well-recognized effects in cardiovascular disorders, to the newly revealed favorable effects in cancer, eye, autoimmune, kidney, gastrointestinal, bone, and autoimmune disorders. Additionally, the current review explores insights into the potential role of natural products as HMG-CoA reductase inhibitors. Future research should focus on the synergistic effects of natural therapies with synthetic statins to improve health outcomes in populations burdened by non-communicable diseases.

Characterization and expression profiles of stress modulated chloroplast targeted DEAD-box RNA helicases in common bread wheat - Faheem Ullah; Ghazala Nawaz (Acta Physiologiae Plantarum, 2026)

Facial onset sensory and motor neuronopathy: a diagnostic challenge - Chinmayi Seemikeri; Deepak Menon; Saraswati Nashi; Faheem Arshad; P. R. Srijithesh; Suvarna Alladi (Acta Neurologica Belgica, 2026)

A novel PHDVPSS method to stabilize dredged sediments and AI model to predict its unconfined compressive strength - Aamir Khan Mastoi; Faheem Ali Arisar; Nadeem ul karim Bhatti; Mahboob Oad; Shumail Mangrio (Marine Georesources & Geotechnology, 2026)

Mitigating cadmium toxicity in rice through tandem application of zinc oxide nanoparticles and Serendipita indica as revealed by multi-omics and NMT-based ion flux analysis - Muhammad Faheem Adil; Muhammd Naeem; Shafaque Sehar; Fanrui Zhou; Syed Muhammad Hassan Askri; Yunqi Liu; Zhong-Hua Chen; Wenwu Zhou; Imran Haider Shamsi (Journal of Hazardous Materials, 2026)

Development of a TiO2-MXene-Nafion nanocomposite based immunosensor for sensitive electrochemiluminescence detection of porcine skin gelatin - Faheem Kareem; Nurul A'’dilah Binti Haji Bakar; Koo Pey Ting; Batrisyia Safwah Mohd Salleh; Mohammad Muhiuddin; Mohammad Rizwanur Rahman; Minhaz Uddin Ahmed (Food Chemistry, 2026)

Vinasse-derived magnetic porous Fe-biochar for synergistic adsorption and non-radical oxidation of bisphenol A: Mechanisms and applications - Han Zheng; Haotian Guo; Peng Dai; Jiaquan Zhang; Dongliang Wang; Muhammad Faheem; Ziguo Liu; Min Tao; Ping Song; Ying Huang (Environmental Research, 2026)

Assessing Spatiotemporal Variability in Soil Moisture under a Changing Climate Using Hydrological Models in Hilly Landscapes - Muhammad Waseem Rasheed; Junfang Cui; Jialiang Tang; Abid Sarwar; Mostafa Moradzadeh; Muhammad Faheem (Water Resources Management, 2026)

Unveiling the Neuroprotective Effect of Paraoxonase 1 in Neurodegenerative Diseases Focusing on Alzheimer’s Disease - Alaa Ismail; Hayder M. Al-kuraishy; Ali I. Al-Gareeb; Athanasios Alexiou; Marios Papadakis; Safaa A. Faheem; Gaber El-Saber Batiha (Molecular Neurobiology, 2026)

Peripheral blood T regulatory cell profiles in repeat-breeder Cattle: Differential responses to seminal components - Arif Pandit; Sofi Imran Ul Umar; Syed M. Shah; Nazir Ganai; Sajad Darzi; Riaz Shah; Faheem Bhat; Abrar Malik; Hilal Yaqoob; Masood Saleem (Theriogenology, 2025)

Thiourea-modified silk cotton carbon as an efficient sulfur host: A green approach for advanced aluminum-sulfur battery - Muhammad Faheem; Arshad Hussain; Ananda Sholeh Rifky Hakim; Muhammad Ali; Abbas Saeed Hakeem; Md. Abdul Aziz (Biomass and Bioenergy, 2025)

Biodegradation of fluorinated β-triketone herbicide tembotrione by a bacterial–fungal consortium - Mohd Faheem Khan; Met Rama; Cormac D. Murphy (Biocatalysis and Agricultural Biotechnology, 2025)

Gut microbiota profile, potential engineering techniques and its genetic and epigenetic implications in poultry health - Nuruliarizki Shinta Pandupuspitasari; Sugiharto Sugiharto; Faheem Ahmed Khan; Muhammad Asif Raza; Dela Ayu Lestari; Asep Setiaji; Ikania Agusetyaningsih (World Journal of Microbiology and Biotechnology, 2025)

Predicting rice yield and impact of climate change on rice production using machine learning models - Khawaja T. Tasneem; Muhammad Umair Shahzad; Javed Rashid; Kamal M. Othman; Tania Zafar; Muhammad Faheem (Theoretical and Applied Climatology, 2025)
Climate change poses a critical threat to agricultural sustainability, with direct implications for the global food supply. Rice, a staple crop throughout Asia, is particularly vulnerable to variations in temperature and rainfall, making it essential to understand how it responds to changing climatic conditions. This study integrates historical climate records, rice yield data, and projections from Global Climate Models (GCMs; CMIP3) to assess the potential effects of climate change on rice production in Punjab, Pakistan. We employed multiple machine learning approaches, including Multiple Linear Regression (MLR), Boosted Tree Regression (BTR), Probabilistic Neural Network (PNN), Generalized Feed-Forward (GFF) Neural Network, Linear Regression (LR), and a Multilayer Perceptron (MLP) Artificial Neural Network. The models were trained and validated using observed climate and yield data from 1990 to 2020. Future yields were projected under three IPCC emission scenarios (SR-A2, SR-A1B, SR-B1) through the year 2050. Model evaluation showed that the Multilayer Perceptron (MLP) achieved the highest predictive performance ( $$R^2$$ = 0.791, R = 0.868, MAE = 0.215, MSE = 0.0869, NMSE = 0.3681), followed by Boosted Tree Regression (BTR; $$R^2$$ = 0.779, R = 0.845, MAE = 0.334, MSE = 0.1308). The Probabilistic Neural Network (PNN) and Generalized Feed-Forward (GFF) model also performed respectably ( $$R^2$$ = 0.745, R = 0.811, MAE = 0.176, MSE = 0.380 and $$R^2$$ = 0.643, R = 0.825, MAE = 0.398, MSE = 0.178, respectively). In contrast, Multiple Linear Regression (MLR) and Linear Regression (LR) performed poorly, with low $$R^2$$ values (0.535), underscoring their inability to capture the non-linear relationships between climate variables and yield. Our analysis identifies maximum temperature as the primary climatic driver of yield loss. Based on the projections, we estimate an average yield decline of 0.12% by 2050. This study demonstrates that non-linear machine learning models, particularly the MLP, are essential for reliable agricultural forecasting under climate change. The results highlight the growing vulnerability of rice production to rising temperatures and provide a robust evidence base for designing adaptation strategies, such as developing heat-tolerant rice varieties, to enhance food security in vulnerable regions.

Lipid-based nanocarriers in combination chemotherapy: a promising strategy for advanced skin cancer management - Jyotiraditya Mall; Md Faheem Haider; Nazish Naseem; Md Azizur Rahman; Irfan Ahmad (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Unveiling genetic diversity and population structure in lentil (Lens culinaris) germplasm through scot markers - Sarmad Ali Qureshi; Muhammad Azhar Nadeem; Meliha Feryal Sarıkaya; Amjad Ali; Muhammed Tatar; Muhammad Tanveer Altafl; Dilek Tekdal; Muhammad Kashif Ilyas; Seyithan Seydoşoğşu; Sezai Ercişli; Kağan Kökten; Faheem Shahzad Baloch (Molecular Biology Reports, 2025)

Improving Soil Fertility, Seed Yield, and Oil Quality of Sunflower Through Application of Processed Animal Manure Under Rainfed Conditions - Ghulam Abbas Shah; Mughees Mustafa; Zheli Ding; Zahid Mahmood; Faheem Khan; Shujaat Hussain Khan; Safdar Ali; Ghulam Mustafa Shah; Imran Mahmood; Muhammad Bilawal Junaid; Munirah Abdullah Al-Dosary; Muhammad Habib Ur Rehman; et al. (International Journal of Plant Production, 2025)

From global challenges to specific solutions: climate change impacts on agriculture with a focus on sorghum through bibliometric analysis - Waqas Liaqat; Muhammad Tanveer Altaf; Muhammad Faheem Jan; Haseeb Ahmad; Ehtisham Hassan Khan; Celaleddin Barutçular; Gönül Cömertpay; Faheem Shehzad Baloch; Heba I. Mohamed (Cereal Research Communications, 2025)

Nanocarrier Strategies in Glioblastoma: Overcoming Barriers to Effective Brain Tumor Therapy - Sara Khan; Md. Faheem Haider; Safia Obaidur Rab (AAPS PharmSciTech, 2025)

Navigating the asymmetric influence of smart grid technology, renewable energy and institutional quality toward a sustainable environment - Daud Abdul; Jiang Wenqi; Arsalan Tanveer; Muhammad Faheem (Environment, Development and Sustainability, 2025)

Endophytic fungi as biocontrol agents: A metabolite-driven approach to crop protection and sustainable agriculture - Muhammad Faiq; Amjad Ali; Shazia Shafique; Sobiya Shafique; Allah Rakha Yaseen; Rimsha Fatima; Muhammad Tanveer Altaf; Faheem Shehzad Baloch (Physiological and Molecular Plant Pathology, 2025)

Next-generation strategies for nitrogen-efficient maize production for a greener tomorrow - Muhammad Faheem Jan; Waqas Liaqat; Muhammad Tanveer Altaf; Muhammad Dawood Ahmadzai; Asia Maqbool; Faheem Shehzad Baloch; Ming Li (Field Crops Research, 2025)

The AMPK/GDF15 Axis: A Novel Target for the Neuroprotective Effects of Metformin in Ischemic Stroke - Ghadah H. Alshehri; Hayder M. Al-kuraishy; Bshra A. Alsfouk; Ali I. Al-Gareeb; Safaa A. Faheem; Athanasios Alexiou; Marios Papadakis; Gaber El-Saber Batiha (Molecular Neurobiology, 2025)
Metformin is an anti-diabetic drug used in the management of type 2 diabetes (T2D). Metformin has different pleiotropic effects, such as anti-inflammatory, antioxidant, antithrombotic, and vasculoprotective. Metformin has neuroprotective effects against neurodegenerative diseases and ischemic stroke. Conversely, metformin may exacerbate the pathogenesis of ischemic stroke. This controversial point may be related to the impact of metformin on the different signaling pathways, such as AMP-activated protein kinase (AMPK) and growth differentiation factor 15 (GDF-15). Many studies have reported the effect of metformin on ischemic stroke, with AMPK signaling only. However, little has been explored about the impact of metformin on the GDF-15 signaling in ischemic stroke. Accordingly, this review aims to discuss the role of metformin in the neuropathology of ischemic stroke regarding the AMPK and GDF-15 signaling pathways.

A machine learning assisted approach to classify rose species and varieties with laser induced breakdown spectroscopy - Maryam Manzoor; Muhammad Faheem; Muhammad Nadeem; Guljan Shreen; Faisal Hayat; Adnan Younis; Yasir Jamil (Analytica Chimica Acta, 2025)

In-season temporal variability of soil carbon and nitrogen pools after half a century of a tillage and crop rotation gradient - Noelymar Gonzalez-Maldonado; Leonardo Deiss; Faheem Ali; Steve W. Culman (Soil and Tillage Research, 2025)

PFOS caused fertility defects and disrupted spermatogenic gene networks in medaka with a transgenerational history of ancestral BPA exposure - Sourav Chakraborty; Seraiah T. Coe; Santosh Anand; Mehwish Faheem; Xuegeng Wang; Ramji Kumar Bhandari (Environmental Research, 2025)

Tuning water transport channels in sulfonated copolymer membranes for highly effective removal of arsenic and selenium from industrial wastewater - Syed Qamber Ali Zaidi; Muhammad Hafi Wadgama; Zaib Jahan; Muhammad Bilal Khan Niazi; Faheem Hassan Akhtar (Desalination, 2025)

Enhancing stability of enzymes for industrial applications: molecular insights and emerging approaches - Mohd Faheem Khan (World Journal of Microbiology and Biotechnology, 2025)

Damage threshold and pathogenicity analysis of Meloidogyne javanica on tomato cv. S22 using the seinhorst model - Rishil Gupta; Khalid Z. Masoodi; Faheem Ahmad (Physiological and Molecular Plant Pathology, 2025)

Molecular screening of stripe rust and powdery mildew resistance genes in European bread wheat using the validated gene-specific SSR markers - Rada Šućur; Amjad Ali; Parnaz Mortazavi; Velimir Mladenov; Bojan Jocković; Jin Ying Gou; Muhammad Azhar Nadeem; Faheem Shehzad Baloch; Yong Suk Chung (Physiological and Molecular Plant Pathology, 2025)

Corrigendum to “Production of manganese telluride-based manganese oxide nano-composite works as a catalyst for effective oxygen evolution reaction” [363 (2024) 130919] - Zainab M. Almarhoon; Karam Jabbour; Sumaira Manzoor; Syed Imran Abbas Shah; Muhammad Faheem Ashiq; Muhammad Yousaf Ur Rehman; Muhammad Fahad Ehsan; Muhammad Najam-ul-Haq; Muhammad Naeem Ashiq (Fuel, 2025)

Carrier-free methylene blue nanomedicine for prolonged hepatic visualization in anatomical hepatectomy: A translational study from bench to bedside - Hu Chen; Minglei Teng; Qihui Hu; Xiaoliu Liang; Hui Liu; Zhenjie Li; Xing Gao; Yisheng Peng; Xiaoyong Wang; Syed Faheem Askari Rizvi; Yi Lv; Hongwei Cheng; et al. (Chemical Engineering Journal, 2025)

Innovative approaches in breast cancer therapy: repurposing nanocarriers for enhanced outcomes - Sana Naaz Siddiqui; Md. Faheem Haider; Md Azizur Rahman (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Nano-spanlastics-loaded dissolving microneedle patches for ketotifen fumarate: advanced strategies for allergic conjunctivitis treatment and molecular insights - Sammar Fathy Elhabal; Mohamed El-Nabarawi; Mohamed Fathi Mohamed Elrefai; Mahmoud H. Teaima; Mai S. Shoela; Gehad M. Khamis; Ahmed Mohsen Faheem; Nada ahmed kholeif; Mahmoud Tarek Sanad (Drug Delivery and Translational Research, 2025)
Allergic conjunctivitis (AC) is the most common inflammatory disease affecting the eye's ocular surface, lid, conjunctiva, and cornea. However, effective ocular drug delivery remains challenging due to physiological barriers such as the corneal barrier. Ketotifen (KF), a widely used antihistamine and mast cell stabilizer, for treating AC and atopic asthma but belongs to the Biopharmaceutical Classification System (BCS II) have poor solubility. This study developed a multiple strategies approach for the first time, utilizing the spanlastics nano-vesicular carriers’ system (SP) containing KF using an ethanol injection method. The optimized KF-SP exhibited the smallest particle size, largest zeta-potential and entrapment efficiency ∼232.5 ± 1.9 nm, -28 ± 0.51 and 73 ± 0.02%, respectively were further incorporated into PVA/PVP polymeric dissolving microneedles (MNs) by using a micromolding technique. Scanning electron microscopy (SEM) analysis confirmed well-defined tips and morphology, and in vitro studies showed a controlled 93% cumulative release over 72 h, with a zero-order kinetic release profile, providing stable therapeutic levels. Pharmacodynamic evaluation using the Ovalbumin/Aluminium hydroxide-induced AC model demonstrated significant reductions in IgE, TNF-α, and IL-6 levels by 68.7%, 71.3%, and 67.6%, respectively, while TGF-β and IL-10 levels increased by 70.1% and 62.7% using ELISA (Enzyme-Linked Immunosorbent Assay). Gene expression analysis (IGF-1, Annexin A1, and Bcl2) further supported the therapeutic potential of this system. In this study, we proved the topical application of the multiple strategies approach KF-SP loaded PVA/PVP MNs patch offers a targeted, sustained release treatment for AC, with promising implications for prolonged ocular therapy. Graphical Abstract

Non-small Cell Lung Cancer, Immunotherapy and the Influence of Gut Microbiome - Muhammad Faheem Raziq; Haseeb Manzoor; Masood Ur Rehman Kayani (Current Microbiology, 2025)

Do financial inclusion and green growth matter for environmental sustainability? A fresh insight through nonlinear model - Muhammad Sajid; Muhammad Akbar Ali Ansari; Arsalan Tanveer; Noreen Safdar; Muhammad Faheem (Clean Technologies and Environmental Policy, 2025)

Impact of sodium dithionite salinity stress on hydrolysis of urea and total nitrogen removal in textile printing wastewater: Insights from anoxic-oxic-anoxic process - Faheem Ahmed Ghori; Ying Wu; Xumeng Lin; Jintao Yu; Hong Chen; Abdul Khalique Jhatial; Qifan Zhou; Mohmadarslan Kutubuddin Sadannavar; Gang Xue (Process Safety and Environmental Protection, 2025)

Impacts of sea level rise and climate change on the sources, preservation and thermal stability of sedimentary organic carbon in the East China Sea inner shelf since the last deglaciation - Muhammad Faheem Ashfaq; Bin Zhao; Lilei Chen; Yang Ding; Nan Wang; Xiwen Ye; Chao Gao; Xiaoyong Duan; Peng Yao (Quaternary Science Reviews, 2025)

Fungal fermented cottonseed husk-derived biochar for highly efficient sulfanilamide degradation: active site regulation and nonradical pathways - Tiantian Xu; Yehan Xiong; Jiangkun Du; David Werner; Muhammad Faheem; Liang Peng; Sen Quan; Zhen Hu; Fang Xu; Jianguo Bao (Journal of Water Process Engineering, 2025)

Approaches for the amelioration of adverse effects of drought stress on soybean plants: from physiological responses to agronomical, molecular, and cutting-edge technologies - Muhammad Faheem Jan; Muhammad Tanveer Altaf; Waqas Liaqat; Changzhuang Liu; Heba I. Mohamed; Ming Li (Plant and Soil, 2025)

Spatio-temporal analysis of air quality in high traffic density zones of Haridwar City, India - Jogendra Singh; Pankaj Kumar; Amol Kale; Anuj Kumar Yadav; Pradip Kumar Maurya; Dinesh Kumar; Faheem Ahamad (Environmental Monitoring and Assessment, 2025)

Weeds-derived compounds and their interaction assessment with Meloidogyne javanica using homology-built protein modeling - Saba Fatima; Faryad Khan; Mohd Asif; Mohammad Shariq; Mahboob Alam; Afroz Aslam; Arshad Khan; Mansoor Ahmad Siddiqui; Rehab O. Elnour; Mohamed Hashem; Faheem Ahmad (Physiological and Molecular Plant Pathology, 2025)

Exploring single-atom catalysis for hydrogen evolution and storage: A DFT insight into first-row transition metal-porphyrin complexes (Porph@TMs) - Faheem Abbas; Saleem Nawaz Khan; Sadaf Bibi; Mariyum Yousaf; Francis Enujekwu; Muhammad Salman Khan; Sami Ullah; Mohammed Ali Assiri (Gas Science and Engineering, 2025)

The efficacy and safety of low-dose triple combination for hypertension treatment: a systematic review and meta-analysis of randomized controlled trials - Mohamed S. Elgendy; Hosam I. Taha; Ahmed Mazen Amin; Yehya Khlidj; Mohamed R. Ezz; Mohamed A. Elgamasy; Ahmed Almezaine; Mohamed A. Faheem; Islam Rajab; Mohamed Abuelazm (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)
Recently, Low-dose triple single-pill combinations (LDTC) have become a promising option for managing hypertension. This review evaluates LDTC’s effectiveness and safety versus standard care, monotherapy, and placebo for blood pressure (BP) control. A systematic review and meta-analysis of randomized controlled trials retrieved from PubMed, EMBASE, WOS, Scopus, and Cochrane from inception to September 2024. The analysis presented risk ratios (RR) for dichotomous outcomes and mean differences (MD) for continuous outcomes, with 95% confidence intervals (CI). PROSPERO ID: CRD42024595331. We identified five eligible trials with a total of 1,709 patients. LDTC had a higher rate of achieving BP < 140/90 at 4 to 6 weeks (wk) (RR: 1.56; CI: 1.41, 1.72; p < 0.01) and at 8 to 12 wk (RR: 1.43; CI: 1.31, 1.57; P < 0.01). Additionally, LDTC significantly reduced the automated office systolic BP at 4 to 6 wk (MD: -8.80; CI: -10.16, -7.44; p < 0.01), 8 to 12 wk (MD: -8.30; CI: -11.18, -5.42; P < 0.01), and at 24 wk (MD: -6.94; CI: -10.56, -3.32; P < 0.01). However, LDTC indicated an increased rate of hypokalemia (RR: 2.25; CI: 1.50, 3.38; P < 0.01), with no difference between both groups in total adverse events (AEs) ( P = 0.44), serious AEs ( P = 0.79), treatment discontinuation due to AEs ( P = 0.91), and the AEs of special interest ( P = 0.54). LDTC therapy is effective and safe for hypertension management but poses potassium depletion. Further large-scale studies are essential to confirm its clinical benefits. Graphical Abstract

Evaluation of groundwater quality of Mirpurkhas District, Sindh, Pakistan, for drinking, irrigation and multivariate analysis - Asadullah Khaskheli; Taj Muhammad Jahangir Khuhawar; Muhammad Yar Khuhawar; Faheem Yar Khuhawar; Muhammad Farooque Lanjwani; Abdul Qayoom Landar (Arabian Journal of Geosciences, 2025)

Antioxidant constituents from Ribes glaciale Wall.: bioassay targeted in-vitro and in-silico evaluation - Rajendra Singh; Rohit Verma; Nitin Sati; Waseem Ahmad Ansari; Mohammad Faheem Khan (Natural Product Research, 2025)

Tirzepatide: a novel therapeutic approach for Alzheimer’s disease - Ghadah H. Alshehri; Hayder M. Al-kuraishy; Huda Jaber Waheed; Ali I. Al-Gareeb; Safaa A. Faheem; Athanasios Alexiou; Marios Papadakis; Gaber El-Saber Batiha (Metabolic Brain Disease, 2025)
Tirzepatide (TRZ) is a dual agonist of glucagon-like peptide 1 (GLP-1) and gastric inhibitory polypeptide (GIP) receptors that were recently approved for the treatment of type 2 diabetes (T2D) and obesity. Of note is that T2D and obesity, by inducing peripheral low-grade inflammation and oxidative stress, provoke the development of central neuroinflammation and oxidative stress. Together, T2D and obesity are regarded as potential risk factors implicated in the development and progression of Alzheimer’s disease (AD), which is the most common neurodegenerative disease and represents the most typical cause of dementia. Hence, targeting low-grade inflammation and oxidative stress in T2D and obesity by TRZ may reduce AD neuropathology. In addition, TRZ can inhibit the production of amyloid beta (Aβ) and associated neuroinflammation, oxidative stress, and neuronal apoptosis. However, the underlying neuroprotective mechanism of TRZ against AD is not entirely explained. Consequently, this mini-review aims to discuss the possible molecular mechanism of TRZ in AD.

Return connectedness and portfolio implications of green equities: A comparison of green and conventional investment modes - Nasir Nadeem; Imran Abbas Jadoon; Faheem Aslam; Paulo Ferreira (Journal of Environmental Management, 2025)

Lophatherum-Gracile driven near-infrared carbon dots inhibit ferroptosis and mitophagy to treat acute kidney injury - Lijuan Yang; Fan Dai; Haitian Tang; Man Li; Yibo An; Yubo Tan; Renyuan Liu; Xinyu Tan; Wenxiang Zhang; Syed Faheem Askari Rizvi; Junjie Zou; Zhixiang Lu; et al. (Chemical Engineering Journal, 2025)

Globally analysis of production of lactic acid by Lactobacillus plantarum AC11S: kinetics using Mittag-Leffler kernel via mathematical modeling - Muhammad Farman; Aqeel Ahmad; Muhammad Faheem; Kottakkaran Sooppy Nisar; Muhammad Saeed Akram; Hijaz Ahmad (Modeling Earth Systems and Environment, 2025)

The use of RGB vegetation indices to predict the buckwheat yield at the flowering stage - E. M. B. M. Karunathilake; Thanh Tuan Thai; Sheikh Mansoor; Anh Tuan Le; Faheem Shehzad Baloch; Yong Suk Chung; Dong-Wook Kim (Journal of Crop Science and Biotechnology, 2025)

Comprehensive Genomic, Mutation, Phylogenetic, and Statistical Analysis of the Monkeypox Virus Across Multiple Countries - Imran Zafar; Faheem kanwal; Muhammad Azmat; Ahsanullah Unar; Ijaz Ali; Waqas Yousaf; Qurat ul Ain; Mohd Ashraf Rather; Nemat Ali; Mohammad Rashid Khan; Amandeep Singh Dhanju; Rohit Sharma (Indian Journal of Microbiology, 2025)

Exploring genetic diversity of Turkish fig (Ficus carica L.) germplasm using inter-Primer Binding Site (iPBS) retrotransposon markers - Viyan Acar Uçer; Erdal Aglar; Parnaz Mortazavi; Sarmad Ali Qureshi; Amjad Ali; Muhammed Tatar; Muhammad Tanveer Altaf; Mehmet Bedir; Sezai Ercişli; Muhammad Azhar Nadeem; Faheem Shehzad Baloch (Genetic Resources and Crop Evolution, 2025)

Chlorophyll fluorescence: a smart tool for maize improvement - Muhammad Faheem Jan; Ming Li; Waqas Liaqat; Muhammad Tanveer Altaf; Changzhuang Liu; Haseeb Ahmad; Ehtisham Hassan Khan; Zain Ali; Celaleddin Barutçular; Heba I. Mohamed (Cereal Research Communications, 2025)

Genome-wide identification of NAC transcription factors in Acer paxii, and their expression dynamics during leaf aging - Yuzhi Fei; Shah Faheem Afzal; Zhu Chen; Yue Zhao; Xin Meng; Jie Ren; Shuiming Zhang (Genes & Genomics, 2025)

Unlocking Alzheimer’s Disease: The Role of BDNF Signaling in Neuropathology and Treatment - Saad Misfer Alqahtani; Hayder M. Al-kuraishy; Ali I. Al Gareeb; Ali K. Albuhadily; Athanasios Alexiou; Marios Papadakis; Loah R. Hemeda; Safaa A. Faheem; Gaber El-Saber Batiha (NeuroMolecular Medicine, 2025)
Alzheimer’s disease (AD) remains one of the most debilitating neurodegenerative disorders, with its pathological hallmark being progressive cognitive decline and memory loss. Recent research has illuminated the crucial role of the brain-derived neurotrophic factor (BDNF) in the central nervous system (CNS), highlighting its impact on neurogenesis, synaptic plasticity, and neuronal survival. Dysregulation of the BDNF signaling axis, particularly the imbalance between its precursor form and mature BDNF, is strongly implicated in the pathophysiology of AD. This review explores the molecular mechanisms through which BDNF modulates AD neuropathology and presents novel therapeutic strategies to activate BDNF signaling. We focus on the potential of BDNF activators, such as TrkB agonists and mimetic molecules, to restore synaptic function and ameliorate cognitive deficits in AD. Furthermore, we examine the challenges in translating these findings into clinical practice, including issues with blood–brain barrier penetration and the need for precise receptor targeting. The review emphasizes the therapeutic potential of repurposed drugs, including statins and metformin, in enhancing BDNF signaling and offers new insights into the future of AD treatment. Ultimately, this work provides a compelling argument for BDNF-based therapies as a promising avenue for mitigating the cognitive decline associated with Alzheimer’s disease, signaling a hopeful direction for future research and clinical trials.

Effects of Turmeric on Manganese-induced Redox Imbalance in Testicular Tissues: Histo-micrometric and Biochemical analyses - Fatima Bashir Ahmad; Chaman Ara; Shaukat Ali; Shagufta Andleeb; Hafiz Abdullah Shakir; Faheem Nawaz; Asmatullah (Cell Biochemistry and Biophysics, 2025)

Investigating wing-body lift interference effects on the dynamics of a novel flight-style AUV with bow-wings: Maneuvering simulations and experimental validations - Faheem Ahmed; Xianbo Xiang; Haotian Wang; Jialei Zhang; Gong Xiang; Shaolong Yang (Ocean Engineering, 2025)

Sustainable adsorbents: Metal oxide-biochar nanocomposites from Maize Stalks and Wild Tamarind residues for dye removal and phytotoxicity assessment - Ruba Munir; Amna Muneer; Gadah Albasher; Faheem Abbas; Saima Noreen (Groundwater for Sustainable Development, 2025)

Elevated volatile organic compounds and odorant emissions from used air filters due to ozone exposure - Muhammad Azher Hassan; Junjie Liu; Jiaru Jiang; Muhammad Faheem; Miao Zhang; Mingyao Yao (Building and Environment, 2025)

Short communication: catechol-O-methyltransferase allelic variation in relation to psychological and hormonal indices of stress in children and adolescents with chromosome 22q11.2 deletion syndrome (22q11.2DS) - Jessie L. Beebe; Cydney R. Martin; Ashley F. P. Sanders; Jeremy Guidry; Fahad Faheem; Joel Atallah; Elliott A. Beaton (Journal of Applied Genetics, 2025)

Towards a sustainable tomorrow: unearthing drivers of energy-saving behavior in Pakistan - Rukhsana Gul Gilal; Waseem Gul Gilal; Faheem Gul Gilal; Naeem Gul Gilal (Environment, Development and Sustainability, 2025)

From pollution to preservation: a dynamic examination of tourism, globalization, and environmental resilience in top-tier economies - Xudan Zheng; Mo Kuang; Muhammad Faheem; Arsalan Tanveer (Clean Technologies and Environmental Policy, 2025)

In-situ quantitative detection of hypochlorous acid in food samples by employing a near-infrared fluorescent probe in association with a portable optical data acquisition system - Yuqing Wang; Rumeng Zhang; Wei Liu; Wuyan Gu; Kun Wang; Muhammad Faheem; Jie Wei; Jing Qian; Lingliang Long (Analytica Chimica Acta, 2025)

Removal of copper (II) by spinel ferrite oxides and rGO composite electrodes in capacitive deionization - Rahat Alam; Muhammad Faheem; Ahmed Alhajaj; Yao He; Linda Zou (Journal of Environmental Chemical Engineering, 2025)

Functional Diversification and Mechanistic Insights of MYB Transcription Factors in Mediating Plant Growth and Development, Secondary Metabolism, and Stress Responses - Safoora Mariyam; Vinay Kumar; Aryadeep Roychoudhury; Gajanan Sampatrao Ghodake; Sowbiya Muneer; Joginder Singh Duhan; Faheem Ahmad; Rajesh Kumar Sharma; Joginder Singh; Chandra Shekhar Seth (Journal of Plant Growth Regulation, 2025)

Seismic safety assessment of buildings and perceptions of earthquake risk among communities in Mingora, Swat, Pakistan - Muhammad Umair Raza; Faheem Butt; Farhan Ahmad; Rana Muhammad Waqas (Innovative Infrastructure Solutions, 2025)
Pakistan has experienced several devastating earthquakes, including the 2005 Kashmir earthquake, which resulted in significant loss of life and damage. Mingora City, located in Seismic Zone 3, is particularly vulnerable and requires seismic evaluations and retrofitting of buildings to prevent future casualties and building collapses. Due to the high costs and complexity of seismic assessments, it is impractical to assess all buildings. This study used the FEMA P-154 Rapid Visual Screening (RVS) method to assess 210 buildings. The study also examined local residents’ risk perceptions through interviews. Findings revealed that most buildings had plan and vertical irregularities, such as short columns or soft storeys, and over 90% of buildings fall within damage grades 4 and 5, highlighting the urgent need for retrofitting. Poor construction quality and lack of maintenance were also noted, with 37% of buildings showing damage. Public awareness of earthquake safety was low, and 89.5% of residents agreed on the need for better education. The study highlights the need for public awareness campaigns on earthquake risks and safety.

Mineral profiling of Turkish wheat genetic resources unveiled their conserved potential for biofortification in combating hidden hunger - Husnu Aktaş; Muhammad Azhar Nadeem; Yusuf Tutuş; Serap Doğan; Mehmet Karaman; İrfan Erdemci; Meng-Lu Wang; Jin-Ying Gou; Faheem Shehzad Baloch (Genetic Resources and Crop Evolution, 2025)

Cost effective image-based phenotyping in Capsicum annuum germplasm for rapid assessment of traits - Ji Eun Park; Sheikh Mansoor; Kibon Ku; Anh Tuan Le; Thai Thanh Tuan; Ho-Cheol Ko; Oh San Su Min; Faheem Shahzad Baloch; Yong Suk Chung (Plant Biotechnology Reports, 2025)

High-performance disposable electrochemical sensors for creatinine derived from hollow CoNi-LDH@Creatinine-imprinted Poly(methacrylic acid) (i-PMA) composites - Muhammad Faheem; Zohaib Saddique; Toheed Akhter; Kun Wang; Jing Qian; Wuyan Gu; Adeel Afzal; Lingliang Long (Analytica Chimica Acta, 2025)

Advancing Chickpea Breeding: Omics Insights for Targeted Abiotic Stress Mitigation and Genetic Enhancement - Muhammad Tanveer Altaf; Waqas Liaqat; Amjad Ali; Amna Jamil; Muhammad Fahad; Muhammad Aneeq Ur Rahman; Faheem Shehzad Baloch; Heba I. Mohamed (Biochemical Genetics, 2025)

Molecular screening of diverse Tomato germplasm for root-knot nematode resistance using the Mi23 marker - Parnaz Mortazavi; Amjad Ali; Muhammed Tatar; Fatih Ölmez; Muhammad Tanveer Altaf; Muhammad Azhar Nadeem; Hayriye Yildiz Dasgan; Boran Ikiz; Tuğçe Temtek; Ömer Faruk Bilgin; Ayşe Mücahitoğlu; Mahmut Bayram; et al. (Physiological and Molecular Plant Pathology, 2025)

Achyranthes aspera-derived compounds mitigate the pathogenesis of Meloidogyne incognita and in silico approach to determine interaction with nematode protein - Amir Khan; Mohd Amir; Mohd Jameel; Azam Raza; Afzal Khan; Mursaleen Baba; Khalid Z. Masoodi; Tahani A.Y. Asseri; Mohamed Hashem; Shpend Shahini; Faheem Ahmad (Physiological and Molecular Plant Pathology, 2025)

The effective use of portland cement as binder replacement in reactive powder-based hybrid asphalt concrete - Behrouz Farahi; Milad Hajipour Manjili; Mahdi Ghahremani; Iman Aghayan; Ahmed Faheem; Konstantin Sobolev (Journal of Cleaner Production, 2025)

Global progress towards the Coal: Tracking coal reserves, coal prices, electricity from coal, carbon emissions and coal phase-out - Muhammad Amir Raza; Abdul Karim; M.M. Aman; Mahmoud Ahmad Al-Khasawneh; Muhammad Faheem (Gondwana Research, 2025)

Corrigendum to “Facile synthesis of CuAl2O4/rGO nanocomposite via the hydrothermal method for supercapacitor applications” [Fuel 357(Part A) (2024) 129688] - Shahzaib Khan; Muhammad Usman; Muhammad Abdullah; Muhammad Suleman Waheed; Muhammad Faheem Ashiq; Muhammad Ishfaq Ahmad; Abdulnasser M. Karami; Muhammad Fahad Ehsan; Sumaira Manzoor; Muhammad Naeem Ashiq (Fuel, 2025)

Role of autophagy in plant growth and adaptation to salt stress - Syed Inzimam Ul Haq; Faheem Tariq; Noor Us Sama; Hadiqa Jamal; Heba I. Mohamed (Planta, 2025)

Application of iPBS-retrotransposons markers for the assessment of genetic diversity and population structure among sugar beet (Beta vulgaris) germplasm from different regions of the world - Gökhan Sadık; Mehtap Yıldız; Bilgin Taşkın; Metin Koçak; Pablo Federico Cavagnaro; Faheem Shehzad Baloch (Genetic Resources and Crop Evolution, 2025)

Impact of sulfur-ash reduction treatment on combustion performance, SOx emissions, and flue gas temperatures of lignite coals: experimental and computational study - Mansoor Ahmed Lakhmir; Faheem Akhter; Jawad Ahmed; Sidra Mushtaq; Haris Jawad Arain; Muhammad Junaid Ahsan (Environmental Science and Pollution Research, 2025)

The dynamic role of income inequality, renewable energy and risk components towards environmental sustainability: fresh insights through CS-ARDL approach - Muhammad Asif Khan; Daud Abdul; Wenping Wang; Arsalan Tanveer; Muhammad Faheem; Taimoor Hassan (Environment, Development and Sustainability, 2025)

Wheat2035: Integrating pan-omics and advanced biotechnology for future wheat design - Yingyin Yao; Weilong Guo; Jinying Gou; Zhaorong Hu; Jie Liu; Jun Ma; Yuan Zong; Mingming Xin; Wei Chen; Qiang Li; Zihao Wang; Ruijie Zhang; et al. (Molecular Plant, 2025)

Decrypting proteomics, transcriptomics, genomics, and integrated omics for augmenting the abiotic, biotic, and climate change stress resilience in plants - Rashmi Choudhary; Faheem Ahmad; Cengiz Kaya; Sudhir Kumar Upadhyay; Sowbiya Muneer; Vinod Kumar; Mukesh Meena; Haitao Liu; Hrishikesh Upadhyaya; Chandra Shekhar Seth (Journal of Plant Physiology, 2025)

Development of tetraploids in tissue culture: modern techniques and biotechnological innovations - Sabeen Rehman Soomro; Salma Naimatullha Soomro; Muhammad Tanveer Altaf; Waqas Liaqat; Muhammad Azhar Nadeem; Faheem Shehzad Baloch; Muhammad Aasim; Heba I. Mohamed (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Turmeric counteracts manganese-associated deteriorations in liver and kidney tissues: histomorphometric and biochemical insights - Fatima Bashir Ahmad; Chaman Ara; Shaukat Ali; Madeeha Arshad; Mehwish Faheem; Rizwan Ullah; Asmatullah (Journal of Molecular Histology, 2025)

Leveraging nanostructured lipid carriers to enhance targeted delivery and efficacy in breast cancer therapy: a comprehensive review - Nazish Naseem; Poonam Kushwaha; Faheem Haider (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Enhanced mechanical and axial resilience of recycled plastic aggregate concrete reinforced with silica fume and fibers - Amna Nasir; Faheem Butt; Farhan Ahmad (Innovative Infrastructure Solutions, 2025)

Applicability of Start Codon Targeted (SCoT) markers for the assessment of genetic diversity in bread wheat germplasm - Muhammad Tanveer Altaf; Muhammad Azhar Nadeem; Amjad Ali; Waqas Liaqat; Mehmet Bedir; Nurettin Baran; Aleksandra Ilić; Muhammad Kashif Ilyas; Abdul Ghafoor; Hamide Dogan; Muhammad Aasim; Faheem Shehzad Baloch (Genetic Resources and Crop Evolution, 2025)
Research endeavors focused on examining genetic diversity play a pivotal role in advancing agricultural practices, as they furnish valuable insights for breeding programs and the preservation of germplasm. Wheat holds significant global importance as a cereal crop, serving as a primary source of sustenance for almost one-third of the global human population. In the current study, a total of 80 bread wheat genotypes were characterized using the start codon targeted (SCoT) marker system. A set of 14 polymorphic primers yielded a cumulative count of 399 bands with an average of 28.05 bands per primer. The range of diversity markers, such as polymorphism information content (0.26–0.59), effective numbers of alleles (1.27–1.59), Shannon’s information index (0.30–0.51), and gene diversity (0.18–0.34), provided evidence of elevated genetic differences within the examined germplasm. According to the findings of the molecular variance analysis, greater genetic variations are found within populations (92%). The model-based structural approach partitioned the 80 bread wheat genotypes into two distinct populations (Population A and B). The diversity indices based on the structures of the populations revealed that population A had greater diversity compared to population B. Both the principal coordinate analysis and the neighbor-joining analysis also differentiated the 80 different bread wheat genotypes based on their respective collection points. The present crop diversity offers great opportunities for enhancing crop quality and increasing tolerance to environmental challenges, both of which will lead to a reduction in the problem of food insecurity.

Regulatory T cells in bovine fertility: Current understanding and future prospects - Arif Pandit; Syed M. Shah; Riaz A. Shah; Sabia Qureshi; R.S. Sethi; Faheem Bhat; Abrar Malik; Oveas Parray; Hilal Yaqoob; Masood Saleem (Animal Reproduction Science, 2025)

Fabrication of Iron Oxide–Based Chitosan/CNF Bio-Green Composite for Pb(II) Removal from Synthetic Wastewater: Isotherm and Regeneration Studies - Faheem Akhter; Jawad Ahmed; Waseem khan; Abdul Rehman Jatoi; Mansoor Ahmed Lakhmir; Muhammad Junaid Ahsan; Haris Jawad Arain; Shareen Bhurgri; Niaz Muhammad Laghari; Irfan Ali Sanjrani (Water Conservation Science and Engineering, 2024)

Exome sequencing revealed variants in SGCA and SIL1 genes underlying limb girdle muscular dystrophy and Marinesco–Sjögren syndrome patients - Ali Faheem; Rizwan Masud; Rabea Nasir; Zeeshan Khalid Awan; Hammad Ali Nasir; Zara Khalid Khan; Hajra Fayyaz; Syed Irfan Raza (Molecular Biology Reports, 2024)

Applicability of SCoT markers in unraveling genetic variation and population structure among sugar beet (Beta vulgaris L.) germplasm - Nazlı Aybar Yalinkiliç; Sema Başbağ; Muhammad Tanveer Altaf; Amjad Ali; Muhammad Azhar Nadeem; Faheem Shehzad Baloch (Molecular Biology Reports, 2024)

A homozygous missense variant in YTHDC2 induces azoospermia in two siblings - Shixiong Tian; Muhammad Faheem; Humayoon Shafique Satti; Jianqiu Xiao; Feng Zhang; Tahir Naeem Khan; Chunyu Liu (Molecular Genetics and Genomics, 2024)

In-silico identification and exploration of small molecule coumarin-1,2,3-triazole hybrids as potential EGFR inhibitors for targeting lung cancer - Sunil Kumar; Iqra Ali; Faheem Abbas; Faiza Shafiq; Ashok Kumar Yadav; Manjunath D. Ghate; Deepak Kumar (Molecular Diversity, 2024)

Network-based drug repurposing identifies small molecule drugs as immune checkpoint inhibitors for endometrial cancer - Faheem Ahmed; Anupama Samantasinghar; Wajid Ali; Kyung Hyun Choi (Molecular Diversity, 2024)

An Assessment of Application Methods of Plant Growth Promoting Rhizobacteria (PGRRs) for Their Growth Promoting Attributes in Sugarcane (Saccharum spp. hybrid) - Saiba Idrees; Samina Mehnaz; Faheem Aftab (Journal of Soil Science and Plant Nutrition, 2024)

Comparative biochemical and physiological responses to the virus-induced mosaic disease in apple (Malus domestica) - Subaya Manzoor; Sajad Un Nabi; Tariq Rasool Rather; M. K. Verma; Shouaa A. Alrobaish; Wasim H. Raja; Javid I. Mir; Tanveer Ahmad Wani; Riyazul Rouf Mir; Faheem Jeelani; Shugufta Parveen; Sheikh Mansoor (Journal of Plant Diseases and Protection, 2024)

Engineering properties assessment and aggregate suitability of the jurassic and eocene limestone: a case study from the Upper Indus Basin, Pakistan - Shuja Ullah; Nazir Ur Rehman; Abdul Rahim Asif; Rizwan Ullah; Liaqat Ali; Muhammad Rizwan; Faheem Ahmed; Tanzeel Ur Rehman (Carbonates and Evaporites, 2024)

GC-MS and molecular docking analysis of mustard seed cake-derived compounds: Evaluating their nematotoxic efficacy against Meloidogyne javanica for sustainable agriculture - Mohd Farhan Khan; Khalid Umar; Javed Ahmad Wagay; Mohd Sajid Ali; Hamad A. Al-Lohedan; Nishant Ranjan; Soumya Pandit; Mohamed M. Hassan; Bander Albogami; Montaser M. Hassan; Arshi Anees; Faheem Ahmad (Physiological and Molecular Plant Pathology, 2024)

Insight into simultaneous urea hydrolysis and total nitrogen removal in textile printing wastewater: Focus on the impact of sodium sulfate salinity - Faheem Ahmed Ghori; Ying Wu; Xumeng Lin; Yueling He; Qianjiang Yu; Hong Chen; Gang Xue (Journal of Environmental Management, 2024)

RNA interference: a promising biotechnological approach to combat plant pathogens, mechanism and future prospects - Amjad Ali; Muhammad Shahbaz; Fatih Ölmez; Noor Fatima; Ummad Ud Din Umar; Md. Arshad Ali; Muhammad Akram; Jaya Seelan Sathiya Seelan; Faheem Shehzad Baloch (World Journal of Microbiology and Biotechnology, 2024)

Zinc and methyl jasmonate improve sugar beet tolerance to high boron stress by enhanced leaf photochemical performance - Jialu Huo; Xiaoyu Zhao; Baiquan Song; Muhammad Faheem Adil; Shafaque Sehar; Xilong Liang; Jiaxin Li; Muhammad Ishfaq; Shangxuan Liu; Songlin Yang (Journal of Environmental Management, 2024)

Editing microbes to mitigate enteric methane emissions in livestock - Faheem Ahmed Khan; Azhar Ali; Di Wu; Chunjie Huang; Hamza Zulfiqar; Muhammad Ali; Bilal Ahmed; Muhammad Rizwan Yousaf; Ezi Masdia Putri; Windu Negara; Muhammad Imran; Nuruliarizki Shinta Pandupuspitasari (World Journal of Microbiology and Biotechnology, 2024)

Machine learning modeling and statistical optimization of dye removal from contaminated water using CTAB-functionalized graphene oxide - Sally AlNaimat; Usman M. Ismail; Ahmed I. Ibrahim; Abdimalik Muse; Kashif Faheem; Mohamed Mustafa; Muhammad S. Vohra; Sagheer A. Onaizi (Water, Air, & Soil Pollution, 2024)

Millets: a nutritional powerhouse for ensuring food security - Vikash Kumar; Mohini Yadav; Simon Kamwele Awala; Johanna Shekupe Valombola; Maneesha S. Saxena; Faheem Ahmad; Saurabh C. Saxena (Planta, 2024)

Strategies and bibliometric analysis of legumes biofortification to address malnutrition - Muhammad Tanveer Altaf; Waqas Liaqat; Amna Jamil; Muhammad Faheem Jan; Faheem Shehzad Baloch; Celaleddin Barutçular; Muhammad Azhar Nadeem; Heba I. Mohamed (Planta, 2024)

Novel zirconium phosphate/MXene/ionic liquid membranes for PEM fuel cells operating up to 145°C - Amani Al-Othman; Muhammad Tawalbeh; Ahmad Ka’aki; Ibrahim Shomope; Muhammad Faheem Hassan (Process Safety and Environmental Protection, 2024)

Engineering of interfacial electric field by g-C3N4/ZnSnO3 heterojunction for excellent photocatalytic applications - Zia Ur Rehman; Sajid Ur Rehman; Muhammad Bilal; Faheem K. Butt; Asif Hussain; Jawad Ahmad Jrar; Kewang Zheng; Yongcai Zhang; Xiaoyong Xu; Xiaozhi Wang; Jianhua Hou (Journal of Cleaner Production, 2024)

Frontiers in bacterial-based green synthesized nanoparticles (NPs): A sustainable strategy for combating infectious plant pathogens - Amjad Ali; Muhammad Aasim; Kübra Çelik; Muhammad Azhar Nadeem; Faheem Shehzad Baloch (Biocatalysis and Agricultural Biotechnology, 2024)

A Bibliometric Analysis of Genome-wide Association Study (GWAS) and Sorghum (Sorghum bicolor L) Based on Web of Science Using VOS Viewer - Muhammad Tanveer Altaf; Waqas Liaqat; Amna Jamil; Muhammad Faheem Jan; Faheem Shehzad Baloch; Heba I. Mohamed (Journal of Soil Science and Plant Nutrition, 2024)

A Critical Review: Breeding Objectives, Genomic Resources, and Marker-Assisted Methods in Sorghum (Sorghum bicolor L.) - Muhammad Tanveer Altaf; Waqas Liaqat; Amna Jamil; Heba I. Mohamed; Muhammad Fahad; Muhammad Faheem Jan; Faheem Shehzad Baloch (Journal of Soil Science and Plant Nutrition, 2024)

Predicting Standard Penetration Test N-value from Cone Penetration Test Data Using Gene Expression Programming - Mehtab Alam; Jianfeng Chen; Muhammad Umar; Faheem Ullah; Muhammad Shahkar (Geotechnical and Geological Engineering, 2024)

Sustainable utilization of clay minerals-rich engineering muck via alkali activation: Optimization of pore structure by thermal treatment - Bingxiang Yuan; Jingkang Liang; Xianwang Li; Baifa Zhang; Qingzi Luo; Sabri Mohanad Muayad Sabri; Faheem Muhammad; Wasei Ragab Azzam; Feng Rao; Peng Yuan (Applied Clay Science, 2024)

A second hit by PFOS exposure exacerbated developmental defects in medaka embryos with a history of ancestral BPA exposure - Seraiah T. Coe; Sourav Chakraborty; Mehwish Faheem; Karabuning Kupradit; Ramji K. Bhandari (Chemosphere, 2024)

Ypresian–Lutetian platform evolution in the Indus Basin, Southwestern Pakistan: An interplay between local and regional tectonic changes - Maqsood Ur Rahman; Muhammad Hanif; Tao Jiang; Wang Qianru; Fulong Ning; Muhammad Sarim; Muhammad Rizwan; Faheem Ahmed (Sedimentary Geology, 2024)

Robust adaptive model-free depth tracking control of under-actuated LAUV with experimental results - Donglei Dong; Xianbo Xiang; Jinjiang Li; Yu Duan; Faheem Ahmed; Shaolong Yang (Ocean Engineering, 2024)

Correction to: Efficient Adsorption of Lead(II) Ions from Artificial Wastewater by Organically Tailored vs TEOS‑Doped Silica Aerogels: Synthesis, Characterization and Isotherm Studies - Faheem Akhter; Heera Lal Soni; Abdul Rauf Jamali; Fernanda Miranda Zoppas; Sobhy M. Ibrahim (Water, Air, & Soil Pollution, 2024)

Stripe rust resistance gene Yr15 in Turkish and Kazakhstan wheat germplasms and the potential of Turkish wild emmer for stripe rust breeding - Faheem Shehzad Baloch; Amjad Ali; Daniyar Tajibayev; Muhammad Azhar Nadeem; Fatih Ölmez; Hüsnü Aktaş; Ahmad Alsaleh; Gönül Cömertpay; Mustafa Imren; Zemran Mustafa; Abdelfattah A. Dababat; Seung Hwan Yang (Genetic Resources and Crop Evolution, 2024)

Zeugodacus fruit flies (Diptera: Tephritidae) host preference analysis by machine learning-based approaches - Naila Nazir; Sehar Fatima; Muhammad Aasim; Faheem Yaqoob; Khalid Mahmood; Seyid Amjad Ali; Shahid Iqbal Awan; Ihsan ul Haq (Computers and Electronics in Agriculture, 2024)

Characterization of Gold-Enhanced Titania: Boosting Cell Proliferation and Combating Bacterial Infestation - Touseef Amna; M. Shamshi Hassan; Jari S. Algethami; Alya Aljuaid; Anas Alfarsi; Rasha Alnefaie; Faheem A. Sheikh; Myung-Seob Khil (Tissue Engineering and Regenerative Medicine, 2024)

Comprehensive journey from past to present to future about seed priming with hydrogen peroxide and hydrogen sulfide concerning drought, temperature, UV and ozone stresses- a review - Rashmi Choudhary; Vishnu Dayal Rajput; Gajanan Ghodake; Faheem Ahmad; Mukesh Meena; Reiaz ul Rehman; Ram Prasad; Rajesh Kumar Sharma; Rachana Singh; Chandra Shekhar Seth (Plant and Soil, 2024)

Insights into the alleviation of cadmium toxicity in rice by nano-zinc and Serendipita indica: Modulation of stress-responsive gene expression and antioxidant defense system activation - Muhammad Faheem Adil; Shafaque Sehar; Zhengxin Ma; Khajista Tahira; Syed Muhammad Hassan Askri; Mohamed A. El-Sheikh; Aqeel Ahmad; Fanrui Zhou; Ping Zhao; Imran Haider Shamsi (Environmental Pollution, 2024)

Exploring the phytochemical, antioxidant, antimicrobial and analgesic potentials of Solanum erianthum as an alternative biological feedstock for producing sustainable biochemicals - Muhammad Ajaib; Sairah Hafeez Kamran; Muhammad Faheem Siddiqui; Muhammad Qasim; Muhammad Azeem; Zainul Abideen; Attiat Elnaggar; Ali El-Keblawy (Biocatalysis and Agricultural Biotechnology, 2024)

Essential oils work synergistically to mitigate pathogenic impact of Meloidogyne incognita, Rhizoctonia solani and Sclerotinia rolfsii - Pooja Bargali; Ravendra Kumar; Ayush Devrani; Sonu Kumar Mahawer; Himani Karakoti; Om Prakash; Shilpi Rawat; Satya Kumar; Dharmendra Singh Rawat; Shiv Kumar Dubey; Chandra Shekhar Seth; Faheem Ahmad (Biocatalysis and Agricultural Biotechnology, 2024)

Exploring the Potential of Straw and Biochar Application on Soil Quality Indicators and Crop Yield in Semi-arid Regions - Rizwan Azim; Qi Wang; Mahran Sadiq; Xujiao Zhou; Dengkui Zhang; Xiaole Zhao; Yanhua Xu; Yuanwei Sun; Wenjia Qi; Jinhui Zhu; Wen Ma; Bing Liu; et al. (Journal of Soil Science and Plant Nutrition, 2024)

Future in the past: paternal reprogramming of offspring phenotype and the epigenetic mechanisms - Di Wu; Kejia Zhang; Kaifeng Guan; Faheem Ahmed Khan; Nuruliarizki Shinta Pandupuspitasari; Windu Negara; Fei Sun; Chunjie Huang (Archives of Toxicology, 2024)

Diltiazem HCl suppresses porcine reproductive and respiratory syndrome virus infection in susceptible cells and in swine - Liangliang Li; Jiayu Wang; Li Chen; Qinghai Ren; Muhammad Faheem Akhtar; Wenhua Liu; Changfa Wang; Shengliang Cao; Wenqiang Liu; Qin Zhao; Yubao Li; Tongtong Wang (Veterinary Microbiology, 2024)

Production of manganese telluride-based manganese oxide nano-composite works as a catalyst for effective oxygen evolution reaction - Zainab M. Almarhoon; Karam Jabbour; Sumaira Manzoor; Syed Imran Abbas Shah; Muhammad Faheem Ashiq; Muhammad Yousaf Ur Rehman; Muhammad Fahad Ehsan; Muhammad Najam-ul-Haq; Muhammad Naeem Ashiq (Fuel, 2024)

Microalgal and activated sludge processing for biodegradation of textile dyes - Ghulam Mustafa; Muhammad Tariq Zahid; Mayur Bharat Kurade; Aliya Alvi; Faheem Ullah; Nikita Yadav; Hyun-Kyung Park; Moonis Ali Khan; Byong-Hun Jeon (Environmental Pollution, 2024)

Genomic characterization of human respiratory syncytial virus circulating in Islamabad, Pakistan, during an outbreak in 2022-2023 - Syed Adnan Haider; Zunera Jamal; Faheem Tahir; Muhammad Salman; Massab Umair (Archives of Virology, 2024)

Formation mechanisms and degradation methods of polycyclic aromatic hydrocarbons in biochar: A review - Canxu Yao; Bing Wang; Jian Zhang; Muhammad Faheem; Qianwei Feng; Masud Hassan; Xueyang Zhang; Xinqing Lee; Shengsen Wang (Journal of Environmental Management, 2024)

Potential of Capparis decidua plant and eggshell composite adsorbent for effective removal of anionic dyes from aqueous medium - Ghulam Mujtaba; Abdul Hai; Mansoor Ul Hassan Shah; Asad Ullah; Yasir Anwar; Furqan Shah; Muhammad Daud; Afzal Hussain; Faheem Ahmed; Fawzi Banat (Environmental Research, 2024)

Biodegradation of petroleum hydrocarbons using a novel bacterial strain isolated from hydrocarbons contaminated soil of Saudi Arabia - Mohammad Hazaimeh; Belal Muneeb Kanaan; Faleh A. AlFaleh; Mahmoud M. Elhaig; Emran Issa Khamaiseh; Qamar Zia; Mohammed Alaidarous; Chandra Shekhar Seth; Noorah Alsowayeh; Faheem Ahmad (Biocatalysis and Agricultural Biotechnology, 2024)

Nutrient and mycoremediation of a global menace ‘arsenic’: exploring the prospects of phosphorus and Serendipita indica-based mitigation strategies in rice and other crops - Shafaque Sehar; Muhammad Faheem Adil; Syed Muhammad Hassan Askri; Elvis Dennis; Mohammad Faizan; Ping Zhao; Fanrui Zhou; Imran Haider Shamsi (Plant Cell Reports, 2024)

Pattern-Triggered Immunity and Effector-Triggered Immunity: crosstalk and cooperation of PRR and NLR-mediated plant defense pathways during host–pathogen interactions - Zarka Nabi; Subaya Manzoor; Sajad Un Nabi; Tanveer Ahmad Wani; Humira Gulzar; Mehreena Farooq; Vivak M. Arya; Faheem Shehzad Baloch; Carmen Vlădulescu; Simona Mariana Popescu; Sheikh Mansoor (Physiology and Molecular Biology of Plants, 2024)

A Comprehensive Review of Hydrogel-Based Drug Delivery Systems: Classification, Properties, Recent Trends, and Applications - Huma Hameed; Saleha Faheem; Ana Cláudia Paiva-Santos; Hafiz Shoaib Sarwar; Muhammad Jamshaid (AAPS PharmSciTech, 2024)

Super capacity of ligand-engineered biochar for sorption of malachite green dye: key role of functional moieties and mesoporous structure - Muhammad Faheem; Muhammad Azher Hassan; Tariq Mehmood; Fahad Al-Misned; Nabeel Khan Niazi; Jianguo Bao; Jiangkun Du (Environmental Science and Pollution Research, 2024)

Exploring differentially expressed genes in Phaseolus vulgaris L. during BCMV infection - Mehmet Zahit Yeken; Ali Çelik; Orkun Emiralioğlu; Vahdettin Çiftçi; Faheem Shehzad Baloch; Göksel Özer (Physiological and Molecular Plant Pathology, 2024)

Variations in rhizosphere soil dominant and pathogenic flora improve boron-efficient Beta vulgaris L. yield under boron deficit - Shangxuan Liu; Baiquan Song; Shafaque Sehar; Muhammad Faheem Adil; Xiaochen Lin; Jialu Huo; Xiaoyu Zhao; Muhammad Riaz (Journal of Cleaner Production, 2024)

Characterization of mRNA Lipid Nanoparticles by Electron Density Mapping Reconstruction: X-ray Scattering with Density from Solution Scattering (DENSS) Algorithm - Huy M. Dao; Khaled AboulFotouh; Aasim Faheem Hussain; Alexander E. Marras; Keith P. Johnston; Zhengrong Cui; Robert O. Williams (Pharmaceutical Research, 2024)

Sorghum: a Star Crop to Combat Abiotic Stresses, Food Insecurity, and Hunger Under a Changing Climate: a Review - Waqas Liaqat; Muhammad Tanveer Altaf; Celaleddin Barutçular; Heba I. Mohamed; Haseeb Ahmad; Muhammad Faheem Jan; Ehtisham Hassan Khan (Journal of Soil Science and Plant Nutrition, 2024)

Unveiling the potential of PANI@MnO2@rGO ternary nanocomposite in energy storage and gas sensing - Ahmad Umar; Sheikh Akbar; Rajesh Kumar; Faheem Ahmed; Sajid Ali Ansari; Ahmed A. Ibrahim; Mohsen A. Alhamami; Noura Almehbad; Hassan Algadi; Tubia Almas; Wen Zeng (Chemosphere, 2024)

Facile synthesis of CuAl2O4/rGO nanocomposite via the hydrothermal method for supercapacitor applications - Shahzaib Khan; Muhammad Usman; Muhammad Abdullah; Muhammad Suleman Waheed; Muhammad Faheem Ashiq; Muhammad Ishfaq Ahmad; Abdulnasser M. Karami; Muhammad Fahad Ehsan; Sumaira Manzoor; Muhammad Naeem Ashiq (Fuel, 2024)

Caring for the environment. How do deforestation, agricultural land, and urbanization degrade the environment? Fresh insight through the ARDL approach - Arsalan Tanveer; Huaming Song; Muhammad Faheem; Abdul Daud (Environment, Development and Sustainability, 2024)

Sensitivity analysis and process optimization for biomass processing in an integrated gasifier-solid oxide fuel cell system - Hafiz Hamza Faheem; Ben Britt; Mateus Rocha; Shou-Han Zhou; Chao'en Li; Weiwei Cai; Liyuan Fan (Fuel, 2024)

Strongly coupled design of zinc oxide-nanorods/copper tin sulfide-nanoflowers nanostructures: An electrochemical study in 4-nitrochlorobenzene detection - Thangavelu Kokulnathan; Ramakrishnan Vishnuraj; Tzyy-Jiann Wang; Biji Pullithadathil; Murali Rangarajan; Faheem Ahmed; Thamraa Alshahrani (Chemical Engineering Journal, 2024)

Retinoic acid signaling in development and differentiation commitment and its regulatory topology - Di Wu; Faheem Ahmed Khan; Kejia Zhang; Nuruliarizki Shinta Pandupuspitasari; Windu Negara; Kaifeng Guan; Fei Sun; Chunjie Huang (Chemico-Biological Interactions, 2024)

Influence of Oxyranylmethanol as a Catalytic Cross-linking Agent over Physiochemical Properties and Pb (II) Adsorption Performance of Resorcinol Formaldehyde Aerogels: a Comparative Study - Faheem Akhter; Abdul Rauf Jamali; Jawad Ahmed; Haris Jawad Arain; Muhammad Junaid Ahsan; Muhammad Naeem Akhtar (Water, Air, & Soil Pollution, 2023)

Production, purification, and characterization of p-diphenol oxidase (PDO) enzyme from lignolytic fungal isolate Schizophyllum commune MF-O5 - Muhammad Faheem; Syed Ali Imran Bokhari; Muhammad Arshad Malik; Bashir Ahmad; Muhammad Riaz; Nafeesa Zahid; Adil Hussain; Abdul Ghani; Hanif Ullah; Waseem Shah; Rashid Mehmood; Khurshid Ahmad; et al. (Folia Microbiologica, 2023)

Molecular, enzymatic responses and in vitro embryonic developmental competency of heat-shocked buffalo embryos co-cultured with granulosa cells monolayer - Marwa S. Faheem; Nasser Ghanem; Romysa Samy; Ashraf Hesham Barkawi (Theriogenology, 2023)

Bearing behaviors and design method of laterally loaded batter pile groups (BPGs) in sand - Shuang Zhao; Juntao Wu; Wenbing Wu; Minjie Wen; Kuihua Wang; Rizvi Syed Muhammad Faheem (Ocean Engineering, 2023)

Ion selective electrosorption by two pseudocapacitive intercalating nanocomposite electrodes - Rahat Alam; Muhammad Faheem; Yao He; Xiao Su; Linda Zou (Desalination, 2023)

Recent advances in fungal xenobiotic metabolism: enzymes and applications - Mohd Faheem Khan; Carina Hof; Patricie Niemcová; Cormac D. Murphy (World Journal of Microbiology and Biotechnology, 2023)
Fungi have been extensively studied for their capacity to biotransform a wide range of natural and xenobiotic compounds. This versatility is a reflection of the broad substrate specificity of fungal enzymes such as laccases, peroxidases and cytochromes P450, which are involved in these reactions. This review gives an account of recent advances in the understanding of fungal metabolism of drugs and pollutants such as dyes, agrochemicals and per- and poly-fluorinated alkyl substances (PFAS), and describes the key enzymes involved in xenobiotic biotransformation. The potential of fungi and their enzymes in the bioremediation of polluted environments and in the biocatalytic production of important compounds is also discussed.

Metal-Doped Carbon Dots (MCDs) as Efficient Nano-adsorbents for Detection, Monitoring, and Degradation of Wastewater Pollutants: Recent Progress, Challenges, and Future Prospects - Faheem Akhter; Jawad Ahmed; Munawar Ali Pinjaro; Fahad Ahmed Shaikh; Haris Jawad Arain; Muhammad Junaid Ahsan (Water, Air, & Soil Pollution, 2023)

Response of the rhizospheric soil microbial community of sugar beet to nitrogen application: A case of black soil in Northeast China - Xiaochen Lin; Baiquan Song; Muhammad Faheem Adil; Milan Kumar Lal; Qiue Jia; Qiuhong Wang; Xin Song (Applied Soil Ecology, 2023)

Transcriptomic analysis of Ralstonia solanacearum in response to antibacterial volatiles of Bacillus velezensis FZB42 - Hafiz Abdul Samad Tahir; Qurban Ali; Faheem Uddin Rajer; Qaisar Shakeel; Waqqas Gillani; Rana Binyamin; Hafiz Muhammad Abdullah Tayyab; Abdur Rashid Khan; Qin Gu; Xuewen Gao; Huijun Wu (Archives of Microbiology, 2023)

Evaluating the influence of green growth, institutional quality and financial inclusion on financial stability: evidence by sustainable finance theory - Muhammad Sajid; Muhammad Akbar Ali Ansari; Arsalan Tanveer; Muhammad Faheem; Asim Waseem (Environmental Science and Pollution Research, 2023)

Applications of remote sensing and near-surface geophysical methods for the investigations of a morainic ridge susceptible to landslide. A case study from the high lands of the Himalayas, Pakistan - Faheem Ullah; Lijun Su; Mehtab Alam; Li Cheng; Elena S. Kazantseva (Journal of Applied Geophysics, 2023)

Endogenous production of 2-phenylethanol by Cunninghamella echinulata inhibits biofilm growth of the fungus - Carina Hof; Mohd Faheem Khan; Cormac D. Murphy (Fungal Biology, 2023)

Simultaneous adsorption of methylene blue and amoxicillin by starch-impregnated MgAl layered double hydroxide: Parametric optimization, isothermal studies and thermo-kinetic analysis - Ghulam Mujtaba; Asad Ullah; Danish Khattak; Mansoor Ul Hassan Shah; Muhammad Daud; Salman Ahmad; Abdul Hai; Faheem Ahmed; Thamraa Alshahrani; Fawzi Banat (Environmental Research, 2023)

Eliciting the Response of Rhizospheric Soil Microbial Community Structure to Zinc Amendment: A Case Study of Sugar Beet Cultivation in Black Soil - Qiue Jia; Baiquan Song; Jialu Huo; Xin Song; Yan Wang; Muhammad Faheem Adil; Muhammad Riaz; Milan Kumar Lal; Hayssam M. Ali (Sugar Tech, 2023)

Ulinastatin ameliorated streptozotocin-induced diabetic nephropathy: Potential effects via modulating the components of gut-kidney axis and restoring mitochondrial homeostasis - Fatma H. Rizk; Amira A. El Saadany; Marwa Mohamed Atef; Rania Nagi Abd-Ellatif; Dina M. El-Guindy; Muhammad T. Abdel Ghafar; Marwa M. Shalaby; Yasser Mostafa Hafez; Shaimaa Samir Amin Mashal; Eman H. Basha; Heba Faheem; Ramez Abd-Elmoneim Barhoma (Pflügers Archiv - European Journal of Physiology, 2023)
Growing evidence supports the role of the gut-kidney axis and persistent mitochondrial dysfunction in the pathogenesis of diabetic nephropathy (DN). Ulinastatin (UTI) has a potent anti-inflammatory effect, protecting the kidney and the gut barrier in sepsis, but its effect on DN has yet to be investigated. This study aimed to assess the potential mitigating effect of UTI on DN and investigate the possible involvement of gut-kidney axis and mitochondrial homeostasis in this effect. Forty male Wistar rats were divided equally into four groups: normal; UTI-treated control; untreated DN; and UTI-treated DN. At the end of the experiment, UTI ameliorated DN by modulating the gut-kidney axis as it improved serum and urinary creatinine, urine volume, creatinine clearance, blood urea nitrogen, urinary albumin, intestinal morphology including villus height, crypt depth, and number of goblet cells, with upregulating the expression of intestinal tight-junction protein claudin-1, and counteracting kidney changes as indicated by significantly decreasing glomerular tuft area and periglomerular and peritubular collagen deposition. In addition, it significantly reduced intestinal and renal nuclear factor kappa B (NF-κB), serum Complement 5a (C5a), renal monocyte chemoattractant protein-1 (MCP-1), renal intercellular adhesion molecule 1 (ICAM1), and renal signal transducer and activator of transcription 3 (STAT3), mitochondrial dynamin related protein 1 (Drp1), mitochondrial fission 1 protein (FIS1), mitochondrial reactive oxygen species (ROS), renal hydrogen peroxide (H 2 O 2 ), and 8-hydroxy-2'-deoxyguanosine (8-OHdG) levels. Furthermore, it significantly increased serum short chain fatty acids (SCFAs), and mitochondrial ATP levels and mitochondrial transmembrane potential. Moreover, there were significant correlations between measured markers of gut components of the gut-kidney axis and renal function tests in UTI-treated DN group. In conclusion, UTI has a promising therapeutic effect on DN by modulating the gut-kidney axis and improving renal mitochondrial dynamics and redox equilibrium.

Alexia without agraphia in an elderly man due to stroke secondary to COVID-19 infection - Faheem Arshad; Vikram Singh; Chandrajit Prasad; Ravi Yadav; Suvarna Alladi (Acta Neurologica Belgica, 2023)

Assessment of meteorological and air quality drivers of elevated ambient ozone in Beijing via machine learning approach - Muhammad Azher Hassan; Muhammad Faheem; Tariq Mehmood; Yihui Yin; Junjie Liu (Environmental Science and Pollution Research, 2023)

Recent advances in chromosome capture techniques unraveling 3D genome architecture in germ cells, health, and disease - Nuruliarizki Shinta Pandupuspitasari; Faheem Ahmed Khan; Chunjie Huang; Azhar Ali; Muhammad Rizwan Yousaf; Farwa Shakeel; Ezi Masdia Putri; Windu Negara; Anis Muktiani; Bambang Waluyo Hadi Eko Prasetiyono; Limbang Kustiawan; Dimar Sari Wahyuni (Functional & Integrative Genomics, 2023)

In-silico identification of small molecule benzofuran-1,2,3-triazole hybrids as potential inhibitors targeting EGFR in lung cancer via ligand-based pharmacophore modeling and molecular docking studies - Sunil Kumar; Iqra Ali; Faheem Abbas; Nimra Khan; Manoj K. Gupta; Manoj Garg; Saroj Kumar; Deepak Kumar (In Silico Pharmacology, 2023)

Research progress of autonomous navigation technology for multi-agricultural scenes - Binbin Xie; Yucheng Jin; Muhammad Faheem; Wenjie Gao; Jizhan Liu; Houkang Jiang; Lianjiang Cai; Yuanxiang Li (Computers and Electronics in Agriculture, 2023)

Synthesis of 3D flower-like zinc-chromium layered double hydroxides: A functional electrode material for furaltadone detection - Thangavelu Kokulnathan; Tzyy-Jiann Wang; Faheem Ahmed; Thamraa Alshahrani (Process Safety and Environmental Protection, 2023)

iPBS-retrotransposons variations: DNA fingerprinting and the evaluation of genetic diversity and population structure in international cowpea germplasm - Faheem Shehzad Baloch; Muhammad Tanveer Altaf; Mehmet Bedir; Muhammad Azhar Nadeem; Muhammed Tatar; Tolga Karaköy; Muhammad Aasim (Genetic Resources and Crop Evolution, 2023)

Enhanced removal of perfluorooctanoic acid with sequential photocatalysis and fungal treatment - Mohd Faheem Khan; Jhimli Paul Guin; Ravindranathan K. Thampi; James A. Sullivan; Cormac D. Murphy (Environmental Science and Pollution Research, 2023)
In this paper, we report the degradation of perfluorooctanoic acid (PFOA), which is a persistent contaminant in the environment that can severely impact human health, by exposing it to a photocatalyst, bismuth oxyiodide (BiOI), containing both Bi 4 O 5 I 2 and Bi 5 O 7 I phases and a fungal biocatalyst ( Cunninghamella elegans ). Individually, the photocatalyst (after 3 h) and biocatalyst (after 48 h) degraded 35–40% of 100 ppm PFOA with 20–30% defluorination. There was a marked improvement in the degree of degradation (90%) and defluorination (60%) when PFOA was first photocatalytically treated, then exposed to the fungus. GC- and LC–MS analysis identified the products formed by the different treatments. Photocatalytic degradation of PFOA yielded short-chain perfluorocarboxylic acids, whereas fungal degradation yielded mainly 5:3 fluorotelomer carboxylic acid, which is a known inhibitor of cytochrome P450-catalysed degradation of PFAS in C. elegans . The combined treatment likely resulted in greater degradation because photocatalysis reduced the PFOA concentration without generating the inhibitory 5:3 fluorotelomer carboxylic acid, enabling the fungus to remove most of the remaining substrate. In addition, new fluorometabolites were identified that shed light on the initial catabolic steps involved in PFOA biodegradation.

Zinc amendment increases the yield and industrial quality of Beta vulgaris L. cultivated in Northeast China - Xiaoyu Zhao; Baiquan Song; Muhammad Ishfaq; Muhammad Faheem Adil; Milan Kumar Lal; Zhenzhen Wu; Qiue Jia; Wengong Huang (Field Crops Research, 2023)

Application of UAV photogrammetry and electrical resistivity tomography for characterization of a complex landslide: a case study from northwest Himalayas, Pakistan - Syed Ahatsham Haider; Matloob Hussain; Aamir Ali; Muhammad Faheem Abbasi; Saad Wani (Natural Hazards, 2023)

Degradation mechanism of Bisphenol S via hydrogen peroxide/persulfate activated by sulfidated nanoscale zero valent iron - Yehan Xiong; Ting Zhou; Jianguo Bao; Jiangkun Du; Muhammad Faheem; Liting Luo (Environmental Science and Pollution Research, 2023)

Optimization of pig manure-derived biochar for ammonium and phosphate simultaneous recovery from livestock wastewater - Sirui Ji; Fang Zhang; Panpan Yao; Chunlan Li; Muhammad Faheem; Qianwei Feng; Miao Chen; Bing Wang (Environmental Science and Pollution Research, 2023)

Synthesis of praseodymium vanadate in deep eutectic solvent medium for electrochemical detection of furaltadone - Tse-Wei Chen; Thangavelu Sakthi Priya; Shen-Ming Chen; Thangavelu Kokulnathan; Faheem Ahmed; Thamraa Alshahrani (Process Safety and Environmental Protection, 2023)

GIS based spatial-temporal distribution of water quality parameters and heavy metals in drinking water: Ecological and health modelling - Elias Bojago; Inderjeet Tyagi; Faheem Ahamad; Surendra Kumar Chandniha (Physics and Chemistry of the Earth, Parts A/B/C, 2023)

Development of Mn-MOF/CuO composites as platform for efficient electrocatalytic OER - Bushra Shabbir; Nidhal Drissi; Karam Jabbour; Abdelaziz Gassoumi; F.F. Alharbi; Sumaira Manzoor; Muhammad Faheem Ashiq; H.A. Alburaih; Muhammad Fahad Ehsan; Muhammad Naeem Ashiq (Fuel, 2023)

An Extensive Comparative Study of Highly Enhanced Pb2+ Adsorption from Synthetic Wastewater by Organically Tailored Silica Aerogels - Faheem Akhter; Abdul Rauf Jamali; Munawar Ali Pinjaro; Abdul Samad Shaikh; Sobhy M. Ibrahim; Maria del Mar Alguacil (Water, Air, & Soil Pollution, 2023)

Artificial neural network and decision tree facilitated prediction and validation of cytokinin-auxin induced in vitro organogenesis of sorghum (Sorghum bicolor L.) - Muhammad Aasim; Seyid Amjad Ali; Muhammad Tanveer Altaf; Amjad Ali; Muhammad Azhar Nadeem; Faheem Shahzad Baloch (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Exploring the genetic diversity and population structure of upland cotton germplasm by iPBS-retrotransposons markers - Nurettin Baran; Flavien Shimira; Muhammad Azhar nadeem; Muhammad Tanveer altaf; Mehtap andirman; Faheem Shehzad Baloch; Mefhar Gültekin Temiz (Molecular Biology Reports, 2023)

Genotype by yield*trait (GYT) biplot analysis: a novel approach for evaluating advance lines of durum wheat - Muhammad Faheem; Saima Mir Arain; Mahboob Ali Sial; Khalil Ahmed Laghari; Abdul Qayyum (Cereal Research Communications, 2023)

Evaluating the relationship between groundwater quality and land use in an urbanized watershed - Umair Rasool; Xinan Yin; Zongxue Xu; Muhammad Faheem; Muhammad Awais Rasool; Jamil Siddique; Muhammad Azher Hassan; Venkatramanan Senapathi (Environmental Science and Pollution Research, 2023)

Halotolerant bacterial biofilms for desalination and water treatment: a pilot study - Sadaf Jahan Gauhar; Aisha Waheed Qurashi; Iram Liaqat; Urooj Zafar; Muhammad Arshad Virk; Chaman Ara; Mehwish Faheem; Muhammad Mubin (Environmental Science and Pollution Research, 2023)

Super disintegrating oromucosal nanofiber patch of zolmitriptan for rapid delivery and efficient brain targeting - Hasham Shafi; Rumaisa Rashid; Sami-ullah Rather; D.V. Siva Reddy; Lubna Azmi; Abdalla Abdal-hay; Salman H. Alrokayan; Haseeb A Khan; Nisar Ahmad Khan; Faheem A. Sheikh (Chemical Engineering Journal, 2023)

Alleviation of Salt Stress in Solanum tuberosum L. by Exogenous Application of Indoleacetic acid and l-Tryptophan - Maria Gull; Zahoor Ahmad Sajid; Faheem Aftab (Journal of Plant Growth Regulation, 2023)

Investigating the location of zone prone to reactivation due to water saturation on landslide debris using electrical resistivity tomography - Faheem Ullah; Li-Jun Su; Elena S. Kazantseva; Mehtab Alam (Bulletin of Engineering Geology and the Environment, 2023)

Stress combination: When two negatives may become antagonistic, synergistic or additive for plants? - Hera NADEEM; Amir KHAN; Rishil GUPTA; Mohamed HASHEM; Saad ALAMRI; Mansoor Ahmad SIDDIQUI; Faheem AHMAD (Pedosphere, 2023)

Hybrid pseudocapacitive sodium titanate/rGO and MXene/rGO nanocomposite electrodes in capacitive deionization - Muhammad Faheem; Rahat Alam; Yao He; Linda Zou (Desalination, 2023)

Microtuberization Potential of Jasmonic Acid, Kinetin and Putrescine in Potato (Solanum tuberosum L.) - Ayesha Pervaiz; Zahoor Ahmad Sajid; Samina Yousaf; Faheem Aftab (American Journal of Potato Research, 2023)

Indian summer monsoon and winter Total Solar Irradiance signals in the tree‐ring δ 18 O from foothills of High Asia, northern Pakistan - Qiang Li; Yu Liu; Ashish Sinha; Gayatri Kathayat; Xiangyu Duan; Ruoshi Liu; Chenxi Xu; Huiming Song; Congxi Fang; Muhammad Faheem Siddiqui; Hai Cheng (International Journal of Climatology, 2023)
A tree‐ring stable oxygen isotope (δ 18 O) chronology was developed for the past 171 years by four Abies pindrow trees growing in southwest foothills of High Asia, northern Pakistan, which is correlated with observed and modelled δ 18 O of precipitation in Islamabad over the instrumental period. The averaged tree‐ring δ 18 O chronology is significantly negative correlated with local ( r = −.651, p n = 38) and regional ( r = −.664, p n = 65) summer precipitation variations. Analysis of vertically integrated water vapour flux and surface wind field suggests that the sampling site is located at the northern limit of the Indian summer monsoon (ISM). Our tree‐ring δ 18 O series is significantly ( p n = 143) negatively correlated with observed Homogenous India rainfall, All Indian rainfall, Core‐Monsoon India rainfall and Northwest India rainfall. This is the first detected ISM signal from tree‐ring δ 18 O over northern Pakistan. Several ISM‐related paleoclimate proxies, including three stalagmites δ 18 O series (Sahiya cave, Jhumar cave and Qunf cave) and a tree‐ring δ 18 O series (Manali), show consistent variability and a correlation coefficient of .566 ( p n = 165) with our tree‐ring δ 18 O, suggesting that a combination of multiple proxies may be potentially useful to understand the full perspective of ISM before instrumental era. In addition, we found that the satellite‐observed winter Total Solar Irradiance exerts influence on the tree‐ring δ 18 O variation ( r = .643, p n = 38), which may be linked to runoff of the Indus River and ISM precipitation.

Public debt and environment degradation in OIC countries: the moderating role of institutional quality - Fatima Farooq; Aurang Zaib; Muhammad Faheem; Muhammad Ali Gardezi (Environmental Science and Pollution Research, 2023)

A rapid and naked-eye on-site monitoring of biogenic amines in foods spoilage - Yuqing Qin; Weikang Ke; Aroosha Faheem; Yueyun Ye; Yonggang Hu (Food Chemistry, 2023)

Efficient Adsorption of Lead(II) Ions from Artificial Wastewater by Organically Tailored vs TEOS-Doped Silica Aerogels: Synthesis, Characterization and Isotherm Studies - Faheem Akhter; Heera Lal Soni; Abdul Rauf Jamali; Fernanda Miranda Zoppas; Sobhy M. Ibrahim (Water, Air, & Soil Pollution, 2023)

Identification of shoot and root genomic regions in response to nitrogen deficiency tolerance in rice through the use of rice back cross recombinant inbred lines (BRILs) - Abdul Malik Solangi; Hira Khanzada; Ghulam Mustafa Wassan; Adnan Rasheed; Ayaz Ali Keerio; Huijie Li; Saba Khanzada; Muhammad Faheem; Mashooq Ali Laghari; Jianmin Bian; Xiaohua Pan; Ziming Wu (Journal of Plant Biochemistry and Biotechnology, 2023)

Characteristics and epidemiological investigation of equid herpesvirus 8 in donkeys in Shandong, China - Tongtong Wang; Cankun Xi; Yue Yu; Wenqiang Liu; Muhammad Faheem Akhtar; Yubao Li; Changfa Wang; Liangliang Li (Archives of Virology, 2023)

Task-specific polymeric membranes to achieve high gas-liquid mass transfer - Muhammad Tayyab Khalid; Tanzila Anjum; Asim Laeeq Khan; Fahad Rehman; Muhammad Aslam; Mazhar Amjad Gilani; Faheem Hassan Akhtar; Mungyu Lee; In Seop Chang; Muhammad Yasin (Chemosphere, 2023)

A review of particulate pollution over Himalaya region: Characteristics and salient factors contributing ambient PM pollution - Muhammad Azher Hassan; Tariq Mehmood; Junjie Liu; Xiaosan Luo; Xinghua Li; Mohsin Tanveer; Muhammad Faheem; Awais Shakoor; Afzal Ahmed Dar; Muhammad Abid (Atmospheric Environment, 2023)

Structural growth of zinc oxide nanograins on carbon cloth as flexible electrochemical platform for hydroxychloroquine detection - Thangavelu Kokulnathan; Tzyy-Jiann Wang; Thangapandian Murugesan; Allen Joseph Anthuvan; Rishi Ranjan Kumar; Faheem Ahmed; Nishat Arshi (Chemosphere, 2023)

Engineered biochar effects on soil physicochemical properties and biota communities: A critical review - Hui Tang; Miao Chen; Pan Wu; Muhammad Faheem; Qianwei Feng; Xinqing Lee; Shengsen Wang; Bing Wang (Chemosphere, 2023)

Survey on traditional and AI based estimation techniques for hydrodynamic coefficients of autonomous underwater vehicle - Faheem Ahmed; Xianbo Xiang; Chaicheng Jiang; Gong Xiang; Shaolong Yang (Ocean Engineering, 2023)

Hydrothermal synthesis of ZnCr-LDH/Tungsten carbide composite: A disposable electrochemical strip for mesalazine analysis - Thangavelu Kokulnathan; Tzyy-Jiann Wang; Faheem Ahmed; Thamraa Alshahrani (Chemical Engineering Journal, 2023)

Recent Advances and Treatment of Emerging Contaminants Through the Bio-assisted Method: A Comprehensive Review - Abdul Sattar Jatoi; Jawad Ahmed; Faheem Akhter; Syed Haseeb Sultan; Ghulam Sever Chandio; Shoaib Ahmed; Zubair Hashmi; Muhammad Azam Usto; Muhammad Shuaib Shaikh; Muhammad Siddique; Ghulamullah Maitlo (Water, Air, & Soil Pollution, 2023)

TEOS-Doped vs Non-TEOS Silica Aerogels: a Comparative Study of Synthesis, Characterization, Isotherm Studies and Performance Evaluation for Pb (II) Removal from Synthetic Wastewater - Faheem Akhter; Abdul Rauf Jamali; Waseem Khan (Water, Air, & Soil Pollution, 2023)

UAV-based remote sensing in plant stress imagine using high-resolution thermal sensor for digital agriculture practices: a meta-review - M. Awais; W. Li; M. J. M. Cheema; Q. U. Zaman; A. Shaheen; B. Aslam; W. Zhu; M. Ajmal; M. Faheem; S. Hussain; A. A. Nadeem; M. M. Afzal; et al. (International Journal of Environmental Science and Technology, 2023)

Assessing the genetic diversity in hawthorn (Crataegus spp.) genotypes using morphological, phytochemical and molecular markers - Ercan Yildiz; Ahmet Sümbül; Mehmet Yaman; Muhammad Azhar Nadeem; Ahmet Say; Faheem Shehzad Baloch; Gheorghe Cristian Popescu (Genetic Resources and Crop Evolution, 2023)

Toxicity of silver, copper oxide, and polyethylene nanoparticles on the earthworm Allolobophora caliginosa using multiple biomarkers - Zeinab Bakr; Mohammed Abdel-Wahab; Ali A. Thabet; Mohamed Hamed; Mohamed Abd El-Aal; Eman Saad; Mehwish Faheem; Alaa El-Din H. Sayed (Applied Soil Ecology, 2023)

Response of Pakistan’s economic growth to macroeconomic variables: an asymmetric analysis - Hafiz M. Sohail; Mirzat Ullah; Kazi Sohag; Faheem Ur Rehman (Environmental Science and Pollution Research, 2022)

A comprehensive review of hydrophobic silica and composite aerogels: synthesis, properties and recent progress towards environmental remediation and biomedical applications - Faheem Akhter; Abdul Rauf Jamali; Mahmood Nabi Abbasi; Mukhtiar Ali Mallah; Ahsan Atta Rao; Shafeeque Ahmed Wahocho; Hafiz Anees-ur-Rehman; Zubair Ahmed Chandio (Environmental Science and Pollution Research, 2022)

Moringa oleifera alleviated oxidative stress, physiological and molecular disruption induced by acute thermal stress in grass carp, Ctenopharyngodon idella - Mehwish Faheem; Saba Khaliq; Rao Zahid Abbas; Abdallah Tageldein Mansour (Fish Physiology and Biochemistry, 2022)

On the inner dynamics between Fossil fuels and the carbon market: a combination of seasonal-trend decomposition and multifractal cross-correlation analysis - Faheem Aslam; Ijaz Ali; Fahd Amjad; Haider Ali; Inza Irfan (Environmental Science and Pollution Research, 2022)

Fluorotelomer alcohols are efficiently biotransformed by Cunninghamella elegans - Mohd Faheem Khan; Cormac D. Murphy (Environmental Science and Pollution Research, 2022)

Heterologous expression of cry1Ia12 insecticidal gene in cotton encodes resistance against pink bollworm, Pectinophora gossypiella (Lepidoptera: Gelechiidae); an alternate insecticidal gene for insect pest management - Muhammad Tariq; Bushra Tabassum; Allah Bakhsh; Abdul Munim Farooq; Zahida Qamar; Faheem Akram; Farah Naz; Abdul Qayyum Rao; Kausar Malik; Idrees Ahmad Nasir (Molecular Biology Reports, 2022)

The paradigms of transport energy consumption and technological innovation as a panacea for sustainable environment: is there any asymmetric association? - Arsalan Tanveer; Huaming Song; Muhammad Faheem; Abdul Daud (Environmental Science and Pollution Research, 2022)

Development of a constitutive model for fibre reinforced cemented Toyoura sand - Muhammad Safdar; Tim Newson; Faheem Shah (European Journal of Environmental and Civil Engineering, 2022)

Air quality assessment of Jaipur city Rajasthan after the COVID-19 lockdown - Mukesh Ruhela; Vedansh Maheshwari; Faheem Ahamad; Vishal Kamboj (Spatial Information Research, 2022)

Comparative genetic, biochemical and physiological analysis of sodium and chlorine in wheat - Muhammad Naeem; Arshad Abbas; Sami Ul-Allah; Waqas Malik; Faheem Shehzad Baloch (Molecular Biology Reports, 2022)

Sustained-release ketamine-loaded lipid-particulate system: in vivo assessment in mice - Weizhi Xu; Faheem Maqbool; Vinod Kumar; James R. Falconer; Cedric S. Cui; Trent M. Woodruff; Karin Borges; Andrew K. Whittaker; Maree T. Smith; Felicity Y. Han (Drug Delivery and Translational Research, 2022)

Co/N co-doped porous carbon as a catalyst for the degradation of RhB by efficient activation of peroxymonosulfate - Hongxia Yu; Dan Ding; Shuailing Zhao; Muhammad Faheem; Weijie Mao; Li Yang; Liwei Chen; Tianming Cai (Environmental Science and Pollution Research, 2022)

Improving Growth, Digestive and Antioxidant Enzymes and Immune Response of Juvenile Grass Carp (Ctenopharyngodon idella) by Using Dietary Spirulina platensis - Mehwish Faheem; Rafia Jamal; Nadia Nazeer; Saba Khaliq; Seyed Hossein Hoseinifar; Hien Van Doan; Marina Paolucci (Fishes, 2022)
The present study was designed to investigate the effect of Spirulina platensis (SP) supplemented diets on the growth performance, digestive enzymes, hepatic antioxidants and innate immunity biomarkers in juvenile grass carp (Ctenopharyngodon idella). Two hundred and forty grass carp juveniles (average weight 4.81 ± 0.13 g) were divided into four treatment groups in triplicates (20 fish/replicate) and fed with diets containing 0, 1, 5, and 10% Spirulina for 90 days. A significant increase in growth (p 0.05) was observed for hepatic superoxide dismutase levels when compared to the control. Significant increases in the skin mucus protease (p

Landslide stability investigation and subsurface deformation mapping by optimizing low-frequency GPR: A mega rainfall susceptible landslide case study (Gilgit Baltistan, Pakistan) - Faheem Ullah; Li-Jun Su; Mehtab Alam; Li Cheng; Mohib Ur Rehman; Aamir Asghar; Gulfam Hussain (Bulletin of Engineering Geology and the Environment, 2022)

Characterization of composite coal seam III–IV of Ramagundam coalfield, Godavari Basin (India): an attempt to evaluate CBM prospects - Harinandan Kumar; Shweta Rai; Ankita Rai; Atif Faheem; Amiya Shankar Naik; Pramod Kumar Rajak; Dilip Kumar Srivastava; Deepak Singh Maurya; Don Chatterjee; Prakash K. Singh (Arabian Journal of Geosciences, 2022)

Influence of priming treatments on germination, seedling growth and survival of China aster [Callistephus chinensis (L.)] - Muneeb Ahmad Wani; Faheem Ullah Khan; Ambreena Din; Imtiyaz Tahir Nazki; Shameen Iqbal; Neelofar Banday (Vegetos, 2022)

Lethal and sublethal effects of flonicamid (50 WG) and spirotetramat (240 SC) on Bemisia tabaci (Homoptera: Aleyrodidae): an age-stage two sex life table study - Aqsa Abbas; Javaid Iqbal; Ali Zeshan; Qurban Ali; Imran Nadeem; Humaira Malik; Tamsila Nazir; Muhammad Faheem Akhter; Bilal Bin Iqbal (Phytoparasitica, 2022)

Assessment of genetic diversity among 131 safflower (Carthamus tinctorius L.) accessions using peroxidase gene polymorphism (POGP) markers - Mehtap Yildiz; Muhammad Tanveer Altaf; Faheem Shehzad Baloch; Metin Koçak; Gökhan Sadık; Cansu Kuzğun; Muhammad Azhar Nadeem; Fawad Ali; Mehmet Bedir; Murat Tunçtürk (Molecular Biology Reports, 2022)

Why is inhalation the most discriminative route of microplastics exposure? - Tariq Mehmood; Muhammad Azher Hassan; Muhammad Faheem; Awais Shakoor (Environmental Science and Pollution Research, 2022)

The effect of climate patterns on rice productivity in Pakistan: an application of Driscoll and Kraay estimator - Faheem Ur Rehman; Ejaz Ahmad (Environmental Science and Pollution Research, 2022)

Evaluating race-to-the-top/bottom hypothesis in high-income countries: controlling emissions cap trading, inbound FDI, renewable energy demand, and trade openness - Bibi Aisha Sadiqa; Khalid Zaman; Faheem Ur Rehman; Abdelmohsen A. Nassani; Mohamed Haffar; Muhammad Moinuddin Qazi Abro (Environmental Science and Pollution Research, 2022)

Hybridization of tumor homing and mitochondria-targeting peptide domains to design novel dual-imaging self-assembled peptide nanoparticles for theranostic applications - Syed Faheem Askari Rizvi; Samiah Shahid; Shuai Mu; Haixia Zhang (Drug Delivery and Translational Research, 2022)

Formulation and Pharmacokinetic Evaluation of Ethyl Cellulose/HPMC-Based Oral Expandable Sustained Release Dosage of Losartan Potassium - Taha Umair Wani; Abdul Aala Fazli; Syed Naiem Raza; Nisar Ahmad Khan; Faheem A. Sheikh (AAPS PharmSciTech, 2022)

Formulation and Evaluation of Topical Linezolid Nanoemulsion for Open Incision Wound in Diabetic Animal Model - Faheem Haider; Barkat Ali Khan; Muhammad Khalid Khan (AAPS PharmSciTech, 2022)

Omics: a tool for resilient rice genetic improvement strategies - Muhammad Naeem; Zeeshan Ali; Anzal Khan; Sami-Ul-Allah; Hassan Javed Chaudhary; Javeria Ashraf; Faheem Shahzad Baloch (Molecular Biology Reports, 2022)

Random mutagenesis in vegetatively propagated crops: opportunities, challenges and genome editing prospects - Mahpara Kashtwari; Sheikh Mansoor; Aijaz A. Wani; Mushtaq Ahmad Najar; Rupesh K. Deshmukh; Faheem Shehzad Baloch; Ishfaq Abidi; Sajad Majeed Zargar (Molecular Biology Reports, 2022)

Energy efficient removal of COD from landfill leachate wastewater using electrocoagulation: parametric optimization using RSM - K. Faheem; S. U. Khan; M. Washeem; S. U. Khan (International Journal of Environmental Science and Technology, 2022)

GIS-based impact assessment and spatial distribution of air and water pollutants in mining area - Mukesh Ruhela; Kaberi Sharma; Rakesh Bhutiani; Surendra Kumar Chandniha; Vikas Kumar; Kaomud Tyagi; Faheem Ahamad; Inderjeet Tyagi (Environmental Science and Pollution Research, 2022)

Applicability of inter-primer binding site iPBS- retrotransposon marker system for the assessment of genetic diversity and population structure of Peruvian rosewood (Aniba rosaeodora Ducke) germplasm - Faheem Shehzad Baloch; Stalin Juan Vasquez Guizado; Muhammad Tanveer Altaf; Ilker Yüce; Yeter Çilesiz; Mehmet Bedir; Muhammad Azhar Nadeem; Rustu Hatipoglu; Juan Carlos Castro Gómez (Molecular Biology Reports, 2022)

Evaluation of insecticidal activity of Beauveria bassiana against different instar larvae of Plutella xylostella by using two different methods of application - Muhammad Shehzad; Muhammad Tariq; Qurban Ali; Asad Aslam; Tariq Mukhtar; Muhammad Faheem Akhtar; Asim Gulzar; Muhammad Faisal (International Journal of Tropical Insect Science, 2022)

Validation of environmental Philips curve in Pakistan: a fresh insight through ARDL technique - Arsalan Tanveer; Huaming Song; Muhammad Faheem; Imran Sharif Chaudhry (Environmental Science and Pollution Research, 2022)

Evaluating pollution damage function through carbon pricing, renewable energy demand, and cleaner technologies in China: blue versus green economy - Muhammad Zaheer Akhtar; Khalid Zaman; Faheem Ur Rehman; Abdelmohsen A. Nassani; Mohamed Haffar; Muhammad Moinuddin Qazi Abro (Environmental Science and Pollution Research, 2022)

Relative effectiveness of eight Trichoderma species against white mould of pea caused by Sclerotinia sclerotiorum - Mujeebur Rahman Khan; Mohammad Haniph Shah; Faheem Ahamad (Indian Phytopathology, 2022)

Antecedents of sustainable e-waste disposal behavior: the moderating role of gender - Mingyue Fan; Abdul Khalique; Sikandar Ali Qalati; Faheem Gul Gillal; Rukhsana Gul Gillal (Environmental Science and Pollution Research, 2022)

RNA interference-mediated knockdown of odorant-binding protein 2 and MP58 gene causes mortality in Myzus persicae - Iqra Mahmood; Amber Afroz; Muhammad Faheem Malik; Nadia Zeeshan; Muhammad Ramzan Khan; Umer Rashid; Muhammad Azmat Ullah Khan; Naeem Mehmood Ashraf; Sadia Alam (International Journal of Tropical Insect Science, 2022)

Impact of COVID-19 on environmental ecosystem - Muhammad Aqeel Ashraf; Muhammad Faheem; Muhammad Azher Hassan (Environmental Science and Pollution Research, 2022)

Moderating role of institutional quality in validation of pollution haven hypothesis in BRICS: a new evidence by using DCCE approach - Imran Sharif Chaudhry; Weihua Yin; Syed Ahtsham Ali; Muhammad Faheem; Qaiser Abbas; Fatima Farooq; Saeed Ur Rahman (Environmental Science and Pollution Research, 2022)

Intron-containing hairpin RNA interference vector for OBP8 show promising mortality in peach potato aphid - Amber Afroz; Safeena Aslam; Umer Rashid; Muhammad Faheem Malik; Nadia Zeeshan; Muhammad Ramzan Khan; Muhammad Qasim Shahzad But; Sabaz Ali Khan (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Does foreign direct investment asymmetrically affect the mitigation of environmental degradation in Malaysia? - Muhammad Faheem; Sadam Hussain; ArsalanTanveer; Noreen Safdar; Muhammad Arshad Anwer (Environmental Science and Pollution Research, 2022)

Short-term analysis on the combined use of sugarcane bagasse ash and rice husk ash as supplementary cementitious material in concrete production - Shahid Hussain Channa; Sajjad Ali Mangi; Naraindas Bheel; Faheem Ahmed Soomro; Shabir Hussain Khahro (Environmental Science and Pollution Research, 2022)

Geophysical prospecting related to earthflow reactivation and hazard assessment: a study based on Huangnibazi slope failure in Sichuan Province, China - Faheem Ullah; Su Lijun; Li Cheng; Liu Zhenyu; Hu Bingli (Bulletin of Engineering Geology and the Environment, 2022)

Unveiling the asymmetric impact of energy consumption on environmental mitigation in the manufacturing sector of Pakistan - Arsalan Tanveer; Huaming Song; Muhammad Faheem; Abdul Daud; Saira Naseer (Environmental Science and Pollution Research, 2021)

Expression studies of stress responsive genes in cotton Gossypium hirsutum L. - Muhammad Naeem; Muhammad Iqbal; Sami Ul-Allah; Hassan Javed Chaudhary; Wajad Nazeer; Javeria Ashraf; Faheem Shahzad Baloch (Molecular Biology Reports, 2021)

Spatial and seasonal variations in particulate matter and gaseous pollutants around integrated industrial estate (IIE), SIDCUL, Haridwar: a case study - Rakesh Bhutiani; Dipali B. Kulkarni; D. R. Khanna; Varun Tyagi; Faheem Ahamad (Environment, Development and Sustainability, 2021)

Homozygosity mapping coupled with whole-exome sequencing and protein modelling identified a novel missense mutation in GUCY2D in a consanguineous Pakistani family with Leber congenital amaurosis - HADIA GUL; ABDUL HALEEM SHAH; RICARDO HARRIPAUL; SUMRA WAJID ABBASI; MUHAMMAD FAHEEM; MUHAMMAD ZUBAIR; MUHAMMAD MUZAMMAL; SAADULLAH KHAN; JOHN B. VINCENT; MUZAMMIL AHMAD KHAN (Journal of Genetics, 2021)

Role of modified diet and gut microbiota in metabolic endotoxemia in mice - Iram Liaqat; Arjumand Iqbal Durrani; Urooj Zafar; Saima Rubab; Mehwish Faheem; Muhammad Mubin; Chand Raza; Nauman Aftab (Archives of Microbiology, 2021)

Exploring the genetic diversity and population structure of scarlet eggplant germplasm from Rwanda through iPBS-retrotransposon markers - Flavien Shimira; Hatice Filiz Boyaci; Yeter Çilesiz; Muhammad Azhar Nadeem; Faheem Shehzad Baloch; Hatıra Taşkin (Molecular Biology Reports, 2021)

dl-β-Amino butyric acid induced resistance in tomato against root-knot nematode Meloidogyne incognita under salt stress condition - Mohd Asif; Faryad Khan; Taruba Ansari; Faheem Ahmad; Moh Tariq; Amir Khan; Mohammad Shariq; Mansoor Ahmad Siddiqui (Indian Phytopathology, 2021)

Lycopene attenuates bisphenol A–induced lung injury in adult albino rats: a histological and biochemical study - Nermeen Mohammed Faheem; Ahmad EL Askary; Amal F. Gharib (Environmental Science and Pollution Research, 2021)

Does financial stability and renewable energy promote sustainable environment in G-7 Countries? The role of income and international trade - Adnan Safi; Salman Wahab; Faheem Zeb; Maaz Amin; Yingying Chen (Environmental Science and Pollution Research, 2021)

Evaluation of Cadmium Chloride-Induced Toxicity in Chicks Via Hematological, Biochemical Parameters, and Cadmium Level in Tissues - Shaukat Ali; Saleha Bashir; Shumaila Mumtaz; Hafiz Abdullah Shakir; Chaman Ara; Farooq Ahmad; Hafiz Muhammad Tahir; Mehwish Faheem; Muhammad Irfan; Azeem Masih; Mazhar Ulhaq; Saiqa Andleeb (Biological Trace Element Research, 2021)

Genetic dissection of days to flowering via genome-wide association studies in Turkish common bean germplasm - Muhammad Azhar Nadeem; Ephrem Habyarimana; Tolga Karaköy; Faheem Shehzad Baloch (Physiology and Molecular Biology of Plants, 2021)

New insights on the utilization of ultrasonicated mustard seed cake: chemical composition and antagonistic potential for root-knot nematode, Meloidogyne javanica - Hera Nadeem; Pieter Malan; Amir Khan; Mohd Asif; Mansoor Ahmad Siddiqui; Simon Tuhafeni Angombe; Faheem Ahmad (Journal of Zhejiang University-SCIENCE B, 2021)

Comparative toxicity of transgenic cotton CEM-33, Bt-906 varieties, and Annona squamosa L., seed extract against biotic potential of Spodoptera litura (Fab.) - Qurban Ali Arain; Muhammad Farhanullah Khan; Habibullah Rana; Amjad Sultan; Zubair Ahmed; Hakim Ali Sahito; Muhammad Asif Farooq; Muhammad Faheem Akbar; Tasneem Kousar (International Journal of Tropical Insect Science, 2021)

Decreased classical monocytes and CD163 expression in TB patients: an indicator of drug resistance - Faheem Shahzad; Noman Bashir; Atia Ali; Shagufta Jabeen; Mohammad Kashif; Khursheed Javaid; Romeeza Tahir; Afia Abbas; Shah Jahan; Nadeem Afzal (Brazilian Journal of Microbiology, 2021)

Tree-ring-based temperature reconstruction from the western Himalayan region in northern Pakistan since 1705 C.E. - Adam Khan; Moinuddin Ahmed; Narayan Prasad Gaire; Javed Iqbal; Muhammad Faheem Siddiqui; Afsheen Khan; Mohib Shah; Ali Hazrat; Najm Us Saqib; Wali Khan Mashwani; Sher Shah; Sanjaya Bhandari (Arabian Journal of Geosciences, 2021)

Hydrodynamic Modelling for a Transportation System of Two Unmanned Underwater Vehicles: Semi-Empirical, Numerical and Experimental Analyses - Faheem Ur Rehman; Luofeng Huang; Enrico Anderlini; Giles Thomas (Journal of Marine Science and Engineering, 2021)
Underwater transportation is an essential approach for scientific exploration, maritime construction and military operations. Determining the hydrodynamic coefficients for a complex underwater transportation system comprising multiple vehicles is challenging. Here, the suitability of a quick and less costly semi-empirical approach to obtain the hydrodynamic coefficients for a complex transportation system comprising two Unmanned Underwater Vehicles (UUVs) is investigated, where the interaction effects between UUVs are assumed to be negligible. The drag results were verified by Computational Fluid Dynamics (CFD) analysis at the steady state. The semi-empirical results agree with CFD in heave and sway; however, they were overpredicted in surge due to ignoring the wake effects. Furthermore, experiments were performed for the validation of the time-domain motion simulations with semi-empirical and CFD results. The simulations which were performed with the CFD drags were close to the experiments. The semi-empirical approach could be relied on once a correction parameter is included to account for the interactive effect between multiple UUVs. Overall, this work makes a contribution by deriving a semi-empirical approach for the dynamic and controlling system of dual UUVs, with CFD and experiments applied to ascertain its accuracy and potential improvement.

Alkaline lipase production by novel meso-tolerant psychrophilic Exiguobacterium sp. strain (AMBL-20) isolated from glacier of northeastern Pakistan - Muhammad Talha Yasin; Yasir Ali; Khurshid Ahmad; Abdul Ghani; Kinza Amanat; Muhammad Mudassir Basheir; Muhammad Faheem; Saddam Hussain; Bashir Ahmad; Adil Hussain; Syed Ali Imran Bokhari (Archives of Microbiology, 2021)

Genetic architecture of wild soybean (Glycine soja Sieb. and Zucc.) populations originating from different East Asian regions - Muhammad Amjad Nawaz; Xiao Lin; Ting-Fung Chan; Hon-Ming Lam; Faheem Shehzad Baloch; Muhammad Amjad Ali; Kirill S. Golokhvast; Seung Hwan Yang; Gyuhwa Chung (Genetic Resources and Crop Evolution, 2021)

Unmodified household coffee maker assisted extraction and purification of anticancer agents from Dillenia indica fruits - Mohsin Ali Khan; Tanveer Ahamad; Mohammad Saquib; Mohd Kamil Hussain; Mohammad Faheem Khan (Natural Product Research, 2021)

Pollutant Removal Efficiency of Electrocoagulation Method from Industrial Wastewater: Comparison with Other Treatment Methods and Key Operational Parameters—a Comparative Study Review - Faheem Akhter; Suhail Ahmed Soomro; Mohammad Siddique; Mansoor Ahmed (Water, Air, & Soil Pollution, 2021)

Identification of genetic variation for salt tolerance in Brassica napus using genome-wide association mapping - Ghulam Mustafa Wassan; Hira Khanzada; Qinghong Zhou; Annaliese S. Mason; Ayaz Ali Keerio; Saba Khanzada; Abdul Malik Solangi; Muhammad Faheem; Donghui Fu; Haohua He (Molecular Genetics and Genomics, 2021)

Advanced microbial fuel cell for waste water treatment—a review - Abdul Sattar Jatoi; Faheem Akhter; Shaukat Ali Mazari; Nizamuddin Sabzoi; Shaheen Aziz; Suhail Ahmed Soomro; Nabisab Mujawar Mubarak; Humair Baloch; Abdul Qayoom Memon; Shoaib Ahmed (Environmental Science and Pollution Research, 2021)

Chemiluminescent-microparticle-immunoassay-based detection and prevalence of human immunodeficiency virus infection in Islamabad, Pakistan - Misbahud Din; Faheem Anwar; Muhammad Ali; Muhammad Yousaf; Bilal Ahmad; Abdullah (Archives of Virology, 2021)

Effect of environmental toxicants on neuronal functions - Supriya Sharma; Sharad Wakode; Anjali Sharma; Nisha Nair; Mahaveer Dhobi; Mushtaq Ahmad Wani; Faheem Hyder Pottoo (Environmental Science and Pollution Research, 2020)

Role of environmental pollutants in Alzheimer’s disease: a review - Reyaz Hassan Mir; Gifty Sawhney; Faheem Hyder Pottoo; Roohi Mohi-ud-din; Sreedhar Madishetti; Sanjay M. Jachak; Zabeer Ahmed; Mubashir Hussain Masoodi (Environmental Science and Pollution Research, 2020)

Frequency of PPAR-γ, FTO and ABCC8 genetic variation in Pakistani cardiovascular smokers - Kanwal Rehman; Ayesha Tahir; Sania Niaz; Sara Shabbir; Komal Jabeen; Amna Faheem; Muhammad Sajid Hamid Akash (Environmental Science and Pollution Research, 2020)

De Novo Assembly and Annotation of the Juvenile Tuber Transcriptome of a Gastrodia elata Hybrid by RNA Sequencing: Detection of SSR Markers - Yunsheng Wang; Muhammad Qasim Shahid; Fozia Ghouri; Faheem Shehzad Baloch (Biochemical Genetics, 2020)

Prediction of poppy thebaine alkaloid concentration using UAS remote sensing - Faheem Iqbal; Arko Lucieer; Karen Barry (Precision Agriculture, 2020)

Environmental toxicology and biogeochemistry of ecosystems - Muhammad Aqeel Ashraf; Muhammad Faheem (Environmental Science and Pollution Research, 2020)

Application of biochar in advanced oxidation processes: supportive, adsorptive, and catalytic role - Faheem; Jiangkun Du; Sang Hoon Kim; Muhammad Azher Hassan; Sana Irshad; Jianguo Bao (Environmental Science and Pollution Research, 2020)

Genetic mapping and identification of new major loci for tolerance to low phosphorus stress in rice - Abdul Malik Solangi; Hira Khanzada; Ghulam Mustafa Wassan; Adnan Rasheed; Ayaz Ali Keerio; Majeeduddin Solangi; Saba Khanzada; Muhammad Faheem; Jianmin Bian; Xiaohua Pan; Rui Cai Han; Xunfeng He; et al. (Physiology and Molecular Biology of Plants, 2020)
Phosphorus (P) is one of the essential macronutrients for rice. In this study, we used 120 rice backcross recombinant inbred lines (BRILs) derived from a cross indica cv. Changhui 891 and japonica cv. 02428. To elucidate the genetic control of P deficiency tolerance in rice, we have used high quality SNPs bin markers to identify some important loci underlying phosphorus deficiency. The bin map was generated which includes 3057 bins covering distance of 1266.5 cM with an average of 0.41 cM between markers. Based on this map, 50 loci, including four novel loci, qSL - 3 , qRL - 11 , qSDW - 1 , qRDW - 1 with phenotypic variance 23.26%, 12.06%, 9.89% associated with P deficiency-related seedling traits were identified. No significant QTLs was found for root length under P+, shoot fresh weight P− and root length, shoot fresh weight for P+, P− and their ratio respectively. Root fresh weight, and root dry weight were strongly correlated to each other, and QTLs for these variables were located on the same chromosome 1 at the same region. Notably, 3 pleiotropic regions is the pioneer of our study, and these regions would facilitate map-based cloning to expedite the MAS selection for developing low phosphorous tolerant varieties. This study not only improves our knowledge about molecular processes associated with P deficiency, but also provides useful information to understand the genetic architecture of low phosphorous tolerance.

Elicitation of resistance through the exploration of acibenzolar-S-methyl (ASM) against Meloidogyne incognita in tomato under salt stress condition - Mohd Asif; Faryad Khan; Taruba Ansari; Faheem Ahmad; Moh Tariq; Amir Khan; Mansoor Ahmad Siddiqui; Shahidul Khair; Wasim Ahmed (Environmental Sustainability, 2020)

Vegetation-environment relationship in conifer dominating forests of the mountainous range of Indus Kohistan in northern Pakistan - Adam Khan; Moinuddin Ahmed; Muhammad Faheem Siddiqi; Mohib Shah; Eduardo Soares Calixto; Afsheen Khan; Paras Shah; Javed Iqbal; Muhammad Azeem (Journal of Mountain Science, 2020)

Bisphenol-A induced antioxidants imbalance and cytokines alteration leading to immune suppression during larval development of Labeo rohita - Mehwish Faheem; Muhammad Adeel; Saba Khaliq; Khalid P. Lone; Alaa El-Din-H-Sayed (Environmental Science and Pollution Research, 2020)

Effect of combined soil application of biochar and oilcakes on Meloidogyne incognita infesting lentil (Lens culinaris cv. Desi) - Taruba Ansari; Mohd Asif; Amir Khan; Moh Tariq; Faheem Ahmad; Faryad Khan; Mansoor Ahmad Siddiqui (Indian Phytopathology, 2020)

Effect of exogenous application of IAA and GA3 on growth, protein content, and antioxidant enzymes of Solanum tuberosum L. grown in vitro under salt stress - Arifa Khalid; Faheem Aftab (In Vitro Cellular & Developmental Biology - Plant, 2020)

Estimation of hydraulic parameters of an unconfined aquifer by using geoelectrical and pumping test data: a case study of the Mandi Bahauddin District, Pakistan - Faheem Ullah; Li-Jun Su; Hafeez Ullah; Aamir Asghar (Arabian Journal of Geosciences, 2020)

Testing the effect of different insecticides on Myzus persicae (Homoptera: Aphididae) in field mustard (Brassicae campestris L.) Czern for possible consideration in an IPM strategy - Muhammad Shahbaz Khan; Muhammad Faheem Akbar; Amjad Sultan; Muhammad Shoaib Saleem; Chand Gul (International Journal of Tropical Insect Science, 2020)

Molecular characterization of genetic diversity and similarity centers of safflower accessions with ISSR markers - Fawad Ali; Muhammad Azhar Nadeem; Ephrem Habyarimana; Abdurrahim Yılmaz; Muhammad Amjad Nawaz; Iftikhar Hussain Khalil; Sezai Ercişli; Gyuhwa Chung; Hassan Javed Chaudhary; Faheem Shehzad Baloch (Brazilian Journal of Botany, 2020)

Efficient Capture of Phosphate and Cadmium Using Biochar with Multifunctional Amino and Carboxylic Moieties: Kinetics and Mechanism - Faheem; Jiangkun Du; Jianguo Bao; Muhammad Azher Hassan; Sana Irshad; Muhammad Afnan Talib; Han Zheng (Water, Air, & Soil Pollution, 2020)

Removal of formaldehyde from the air with a suspended growth bioreactor - Ru Wang; Xuemei Li; Yong Feng; Faheem Tariq; Kunzhi Li; Yulin Wei; Jianhua Chen; Ciqing Jiang; Limei Tian; Yongqin Geng; Enming Miao; Chengming Zhang; et al. (International Journal of Environmental Research, 2019)

Performance evaluation of nanosilica-modified asphalt binder - Faheem Sadiq Bhat; Mohammad Shafi Mir (Innovative Infrastructure Solutions, 2019)

Detection of QTLs for outcrossing-related traits in rice (Oryza sativa L.) by association mapping and the RSTEP-LRT method - Lal Bux; Dalu Li; Muhammad Faheem; Ognigamal Sowadan; Zhiyao Dong; Erbao Liu; Mehtab Ali; Yanhui Li; Helder Manuel Sitoe; Abdul Aziz Mirani; Delin Hong (Euphytica, 2019)

Identification of QTLs associated with p-coumaric acid and ferulic acid in barley - Zhigang Han; Huaizhou Gao; Lingzheng Ye; Muhammad Faheem Adil; Muhammad Ahsan; Guoping Zhang (Euphytica, 2019)

Dust exposure risk from stone crushing to workers and locally grown plant species in Quetta, Pakistan - Saadullah Khan Leghari; Mudassir Asrar Zaidi; Muhammad Faheem Siddiqui; Atta Muhammed Sarangzai; Sana-Ur-Rehman Sheikh; Arsalan (Environmental Monitoring and Assessment, 2019)

Solidification/stabilization of municipal solid waste incineration fly ash using uncalcined coal gangue–based alkali-activated cementitious materials - Shujie Zhao; Faheem Muhammad; Lin Yu; Ming Xia; Xiao Huang; Binquan Jiao; Ning Lu; Dongwei Li (Environmental Science and Pollution Research, 2019)

Characterization of recombinant endo-1,4-β-xylanase of Bacillus halodurans C-125 and rational identification of hot spot amino acid residues responsible for enhancing thermostability by an in-silico approach - Malik Siddique Mahmood; Faiz Rasul; Mahjabeen Saleem; Amber Afroz; Muhammad Faheem Malik; Naeem Mehmood Ashraf; Umar Rashid; Shumaila Naz; Nadia Zeeshan (Molecular Biology Reports, 2019)

Synergistic effect of piperonyl butoxide and emamectin benzoate on enzymatic activities in resistant populations of red flour beetle, Tribolium castaneum Herbst (Coleoptera: Tenebrionidae) - Daud Ahmad Awan; Faheem Ahmad; Mushtaq A. Saleem; Abdul Rauf Shakoori (Environmental Science and Pollution Research, 2019)

Stable isotope probing of active methane oxidizers in rice field soils from cold regions - Nasrin Sultana; Jun Zhao; Yan Zheng; Yuanfeng Cai; Muhammad Faheem; Xianlong Peng; Weidong Wang; Zhongjun Jia (Biology and Fertility of Soils, 2019)

Hereditary brain tumor with a homozygous germline mutation in PMS2: pedigree analysis and prenatal screening in a family with constitutional mismatch repair deficiency (CMMRD) syndrome - Shahid Mahmood Baig; Ambrin Fatima; Muhammad Tariq; Tahir Naeem Khan; Zafar Ali; Mohammad Faheem; Humera Mahmood; Patrick Killela; Matthew Waitkus; Yiping He; Fangping Zhao; Sizhen Wang; et al. (Familial Cancer, 2019)

Characterization of Cellulose Synthase A (CESA) Gene Family in Eudicots - Muhammad Amjad Nawaz; Xiao Lin; Ting-Fung Chan; Muhammad Imtiaz; Hafiz Mamoon Rehman; Muhammad Amjad Ali; Faheem Shehzad Baloch; Rana Muhammad Atif; Seung Hwan Yang; Gyuhwa Chung (Biochemical Genetics, 2019)

The Synergistic Effect of Raloxifene, Fluoxetine, and Bromocriptine Protects Against Pilocarpine-Induced Status Epilepticus and Temporal Lobe Epilepsy - Faheem Hyder Pottoo; Nahida Tabassum; Md. Noushad Javed; Shah Nigar; Rouqia Rasheed; Ayash Khan; Md. Abul Barkat; Md. Sabir Alam; Amir Maqbool; Mohammad Azam Ansari; George E. Barreto; Ghulam Md Ashraf (Molecular Neurobiology, 2019)

Modulation of brain kisspeptin expression after bisphenol-A exposure in a teleost fish, Catla catla - Mehwish Faheem; Nusrat Jahan; Saba Khaliq; Khalid Parvez Lone (Fish Physiology and Biochemistry, 2019)

Paclitaxel-loaded Nanolipidic Carriers with Improved Oral Bioavailability and Anticancer Activity against Human Liver Carcinoma - Harshita; Md Abul Barkat; Md Rizwanullah; Sarwar Beg; Faheem Hyder Pottoo; Sahabjada Siddiqui; Farhan J. Ahmad (AAPS PharmSciTech, 2019)

177Lu-DOTA-coupled minigastrin peptides: promising theranostic agents in neuroendocrine cancers - Syed Faheem Askari Rizvi; Syed Ali Raza Naqvi; Samina Roohi; Tauqir A. Sherazi; Rashid Rasheed (Molecular Biology Reports, 2018)

Analgesic, anti-inflammatory and anticancer activities of Combretin A and Combretin B isolated from Combretum fragrans F. HOFFM (Combretaceae) leaves - Marius Mbiantcha; Jabeen Almas; Amadou Dawe; Aisha Faheem; Zafar Sidra (Inflammopharmacology, 2018)

Gold and Silver Nanoparticles Biomimetically Synthesized Using Date Palm Pollen Extract-Induce Apoptosis and Regulate p53 and Bcl-2 Expression in Human Breast Adenocarcinoma Cells - Hussaina Banu; N. Renuka; S.M. Faheem; Raees Ismail; Vinita Singh; Zahra Saadatmand; Saad Sultan Khan; Kavya Narayanan; Alma Raheem; Kumpati Premkumar; Geetha Vasanthakumar (Biological Trace Element Research, 2018)

Enhanced cutaneous wound healing in rats following topical delivery of insulin-loaded nanoparticles embedded in poly(vinyl alcohol)-borate hydrogels - Dalia H. Abdelkader; Murtaza M Tambuwala; Christopher A. Mitchell; Mohamed A. Osman; Sanaa A. El-Gizawy; Ahmed M. Faheem; Mohamed El-Tanani; Paul A. McCarron (Drug Delivery and Translational Research, 2018)

Use of Eucalyptus camaldulensis as Biosorbent for Lead Removal from Aqueous Solution - Muhammad Ashraf Sabri; Taleb Hassan Ibrahim; Mustafa Ibrahim Khamis; Sameer Al-Asheh; Muhammad Faheem Hassan (International Journal of Environmental Research, 2018)

Ascarosides Promote the Prevalence of Ophiostomatoid Fungi and an Invasive Pathogenic Nematode, Bursaphelenchus xylophilus - Lilin Zhao; Faheem Ahmad; Min Lu; Wei Zhang; Jacob D. Wickham; Jianghua Sun (Journal of Chemical Ecology, 2018)

Effect of pure culture and culture filtrates of Trichoderma species on root-knot nematode, Meloidogyne incognita infesting tomato - Mujeebur Rahman Khan; Irfan Ahmad; Faheem Ahamad (Indian Phytopathology, 2018)

New natural product -an efficient antimicrobial applications of new newly synthesized pyrimidine derivatives by the electrochemical oxidation of hydroxyl phenol in the presence of 2-mercapto-6-(trifluoromethyl) pyrimidine-4-ol as nucleophile - Zia Ul Haq Khan; Amjad Khan; Pingyu Wan; Arif Ullah Khan; Kamran Tahir; Nawshad Muhammad; Faheem Ullah Khan; Hidayat Ullah Shah; Zia Ullah Khan (Natural Product Research, 2018)

Effects of high fluoride content in livestock drinking water on milk samples of different cattle in endemic area of Pakistan: risk assessment for children - Tasneem Gul Kazi; Kapil Dev Brahman; Hassan Imran Afridi; Faheem Shah; Mohammad Balal Arain (Environmental Science and Pollution Research, 2018)

Validation of reference genes for expression analysis in a teleost fish (Catla catla Hamilton) exposed to an endocrine-disrupting chemical, bisphenol-A - Mehwish Faheem; Nusrat Jahan; Saba Khaliq; Khalid Parvez Lone (Rendiconti Lincei. Scienze Fisiche e Naturali, 2018)

Nanosuspension-Based Aloe vera Gel of Silver Sulfadiazine with Improved Wound Healing Activity - Md Abul Barkat; Harshita; Iqbal Ahmad; Raisuddin Ali; Satya Prakash Singh; Faheem Hyder Pottoo; Sarwar Beg; Farhan Jalees Ahmad (AAPS PharmSciTech, 2017)

Differential immune responses of Monochamus alternatus against symbiotic and entomopathogenic fungi - Wei Zhang; Jie Meng; Jing Ning; Peijun Qin; Jiao Zhou; Zhen Zou; Yanhong Wang; Hong Jiang; Faheem Ahmad; Lilin Zhao; Jianghua Sun (Science China Life Sciences, 2017)
Monochamus alternatus , the main vector beetles of invasive pinewood nematode, has established a symbiotic relationship with a native ectotrophic fungal symbiont, Sporothrix sp. 1, in China. The immune response of M. alternatus to S. sp. 1 in the coexistence of beetles and fungi is, however, unknown. Here, we report that immune responses of M. alternatus pupae to infection caused by ectotrophic symbiotic fungus S . sp. 1 and entomopathogenic fungus Beauveria bassiana differ significantly. The S . sp. 1 did not kill the beetles while B. bassiana killed all upon injection. The transcriptome results showed that the numbers of differentially expressed genes in M. alternatus infected with S . sp. 1 were 2-fold less than those infected with B. bassiana at 48 hours post infection. It was noticed that Toll and IMD pathways played a leading role in the beetle’s immune system when infected by symbiotic fungus, but upon infection by entomopathogenic fungus, only the Toll pathway gets triggered actively. Furthermore, the beetles could tolerate the infection of symbiotic fungi by retracing their Toll and IMD pathways at 48 h. This study provided a comprehensive sequence resource of M. alternatus transcriptome for further study of the immune interactions between host and associated fungi.

RNA-Seq reveals differential expression patterns of genes associated with carotenoid accumulation in loquat - Ting-ting Zheng; Zhi-ke Zhang; Muhammad Qasim Shahid; Wei-ling Wei; Faheem Shehzad Baloch; Jin-cheng Wu; Shun-quan Lin; Xiang-hui Yang (Acta Physiologiae Plantarum, 2017)

Multifactorial level of extremostability of proteins: can they be exploited for protein engineering? - Debamitra Chakravorty; Mohd Faheem Khan; Sanjukta Patra (Extremophiles, 2017)

The key role of biogenic manganese oxides in enhanced removal of highly recalcitrant 1,2,4-triazole from bio-treated chemical industrial wastewater - Ruiqin Wu; Haobo Wu; Xinbai Jiang; Jinyou Shen; Muhammad Faheem; Xiuyun Sun; Jiansheng Li; Weiqing Han; Lianjun Wang; Xiaodong Liu (Environmental Science and Pollution Research, 2017)

High bioavailability curcumin: an anti-inflammatory and neurosupportive bioactive nutrient for neurodegenerative diseases characterized by chronic neuroinflammation - Faheem Ullah; Andy Liang; Alejandra Rangel; Erika Gyengesi; Garry Niedermayer; Gerald Münch (Archives of Toxicology, 2017)

The cohesion stabilizer sororin favors DNA repair and chromosome segregation during mouse oocyte meiosis - Chun-Jie Huang; Yi-Feng Yuan; Di Wu; Faheem Ahmed Khan; Xiao-Fei Jiao; Li-Jun Huo (In Vitro Cellular & Developmental Biology - Animal, 2017)

A journey beyond apoptosis: new enigma of controlling metastasis by pro-apoptotic Par-4 - Reyaz Ur Rasool; Debasis Nayak; Souneek Chakraborty; Archana Katoch; Mir Mohd Faheem; Hina Amin; Anindya Goswami (Clinical & Experimental Metastasis, 2016)

Anticoccidial effect of mananoligosacharide against experimentally induced coccidiosis in broiler - Naila Chand; Hassan Faheem; Rifat Ullah Khan; Muhammad Subhan Qureshi; Ibrahim A. Alhidary; Alaeldein M. Abudabos (Environmental Science and Pollution Research, 2016)

The grain Hardness locus characterized in a diverse wheat panel (Triticum aestivum L.) adapted to the central part of the Fertile Crescent: genetic diversity, haplotype structure, and phylogeny - Salar Shaaf; Rajiv Sharma; Faheem Shehzad Baloch; Ekaterina D. Badaeva; Helmut Knüpffer; Benjamin Kilian; Hakan Özkan (Molecular Genetics and Genomics, 2016)

Protective Effect of Lupeol Against Lipopolysaccharide-Induced Neuroinflammation via the p38/c-Jun N-Terminal Kinase Pathway in the Adult Mouse Brain - Haroon Badshah; Tahir Ali; Shafiq-ur Rehman; Faiz-ul Amin; Faheem Ullah; Tae Hyun Kim; Myeong Ok Kim (Journal of Neuroimmune Pharmacology, 2016)

Effect of exogenous application of 24-epibrassinolide on growth, protein contents, and antioxidant enzyme activities of in vitro-grown Solanum tuberosum L. under salt stress - Arifa Khalid; Faheem Aftab (In Vitro Cellular & Developmental Biology - Plant, 2016)

Lead Assessment in Biological Samples of Children with Different Gastrointestinal Disorders - Faheem Shah; Naeem Ullah; Tasneem Gul Kazi; Ajmal Khan; Ghulam Abbas Kandhro; Hassan Imran Afridi; Mohammad Balal Arain; Zahid Khan; Umar Farooq (Biological Trace Element Research, 2016)

Effect of ethylene glycol dimethacrylate on swelling and on metformin hydrochloride release behavior of chemically crosslinked pH–sensitive acrylic acid–polyvinyl alcohol hydrogel - Muhammad Faheem Akhtar; Nazar Muhammad Ranjha; Muhammad Hanif (DARU Journal of Pharmaceutical Sciences, 2015)

Estimation of calcium, magnesium, cadmium, and lead in biological samples from paralyzed quality control and production steel mill workers - Hassan Imran Afridi; Farah Naz Talpur; Tasneem Gul Kazi; Naveed Kazi; Sadaf Sadia Arain; Faheem Shah (Environmental Monitoring and Assessment, 2015)

Toxic metals signature in the human seminal plasma of Pakistani population and their potential role in male infertility - Ambreen Zafar; Syed Ali Musstjab Akber Shah Eqani; Nazish Bostan; Alessandra Cincinelli; Faheem Tahir; Syed Tahir Abbas Shah; Alamdar Hussain; Ambreen Alamdar; Qingyu Huang; Siyuan Peng; Heqing Shen (Environmental Geochemistry and Health, 2015)

Multiple protective mechanisms of alpha-lipoic acid in oxidation, apoptosis and inflammation against hydrogen peroxide induced toxicity in human lymphocytes - Mahban Rahimifard; Mona Navaei-Nigjeh; Maryam Baeeri; Faheem Maqbool; Mohammad Abdollahi (Molecular and Cellular Biochemistry, 2015)

Genetic Linkage Map of Anatolian Durum Wheat Derived from a Cross of Kunduru-1149 × Cham1 - Ahmad Alsaleh; Faheem Shehzad Baloch; Muazzez Derya; Mohamad Azrak; Benjamin Kilian; Hakan Özkan; Miloudi Nachit (Plant Molecular Biology Reporter, 2015)

Potential role of phytohormones and plant growth-promoting rhizobacteria in abiotic stresses: consequences for changing environment - Shah Fahad; Saddam Hussain; Asghari Bano; Shah Saud; Shah Hassan; Darakh Shan; Faheem Ahmed Khan; Fahad Khan; Yutiao Chen; Chao Wu; Muhammad Adnan Tabassum; Ma Xiao Chun; et al. (Environmental Science and Pollution Research, 2015)

Recent developments in therapeutic protein expression technologies in plants - Shah Fahad; Faheem Ahmed Khan; Nuruliarizki Shinta Pandupuspitasari; Muhammad Mahmood Ahmed; Yu Cai Liao; Muhammad Tahir Waheed; Muhammad Sameeullah; Darkhshan; Saddam Hussain; Shah Saud; Shah Hassan; Amanullah Jan; et al. (Biotechnology Letters, 2015)

Estimation of Copper and Iron Burden in Biological Samples of Various Stages of Hepatitis C and Liver Cirrhosis Patients - Salma Aslam Arain; Tasneem G Kazi; Hassan Imran Afridi; Farah Naz Talpur; Moina Akhtar Mughal; Faheem Shah; Sadaf Sadia Arain; Abdul Haleem Panhwar (Biological Trace Element Research, 2014)

Disease resistance in rice and the role of molecular breeding in protecting rice crops against diseases - Shah Fahad; Lixiao Nie; Faheem Ahmed Khan; Yutiao Chen; Saddam Hussain; Chao Wu; Dongliang Xiong; Wang Jing; Shah Saud; Farhan Anwar Khan; Yong Li; Wei Wu; et al. (Biotechnology Letters, 2014)

Silk fibroin based hydrogel for regeneration of burn induced wounds - Hyung Woo Ju; Ok Joo Lee; Bo Mi Moon; Faheem A. Sheikh; Jung Min Lee; Jung-Ho Kim; Hyun Jung Park; Dong Wook Kim; Min Chae Lee; Soo Hyeon Kim; Chan Hum Park; Hae Ran Lee (Tissue Engineering and Regenerative Medicine, 2014)

Two new phenolic compounds from Ficus rumphii and their antiproliferative activity - Mehtab Parveen; Ali Mohammed Malla; Mahboob Alam; Faheem Ahmad; P.S. Pereira Silva; Manuela Ramos Silva (Natural Product Research, 2014)

Exposure of lead to mothers and their new born infants, residents of industrial and domestic areas of Pakistan - Tasneem G. Kazi; Faheem Shah; Haffeezur Rehman Shaikh; Hassan Imran Afridi; Afzal Shah; Naeemullah; Sadaf Sadia Arain (Environmental Science and Pollution Research, 2014)

Prevalence of various chromosomal disorders diagnosed in a selected population suspected of having genetic diseases from different regions of the valley of Kashmir, North India - Arshad A. Pandith; Tahir M. Malla; Fayaz A. Dar; Shahnawaz A. Sheikh; Qayser Yousuf; Shehjar Faheem; Farhat Shawl; Niyaz A. Azad; Shahid Baba; Mushtaq A. Siddiqi; Zafar A. Shah (The Nucleus, 2013)

Investigation of Alteration in the Levels of Iron and Copper in Scalp Hair Samples of Patients Having Different Types of Viral Hepatitis - Salma Aslam Arain; Hassan Imran Afridi; Tasneem G. Kazi; Farah Naz Talpur; Faheem Shah; Sadaf Sadia Arain; Abdul Haleem Panhwar; Kapil Dev Brahman (Biological Trace Element Research, 2013)

iPBS-Retrotransposons-based genetic diversity and relationship among wild annual Cicer species - Enver Ersoy Andeden; Faheem S. Baloch; Muazzez Derya; Benjamin Kilian; Hakan Özkan (Journal of Plant Biochemistry and Biotechnology, 2013)

Homology modeling of LmxMPK4 of Leishmania mexicana and virtual screening of potent inhibitors against it - Chhedi Lal Gupta; Mohd. Kalim Ahmad Khan; Mohd. Faheem Khan; Ashok K. Tiwari (Interdisciplinary Sciences: Computational Life Sciences, 2013)

Determination of Lead in Biological Samples of Children with Different Physiological Consequences Using Cloud Point Extraction Method - Faheem Shah; Tasneem Gul Kazi; Naeem Ullah; Hassan Imran Afridi (Biological Trace Element Research, 2013)

9,10- seco -9,19-cyclolanostane triterpene from Salix caprea L. (Goat Willow) - Mudasir A. Tantry; Saba Shah; Mohammad Y. Dar; Mohammad M. Mir; Khalid Ghazanfar; Faheem A. Sheikh; Mohammad A. Khuroo; Seema Akbar (Natural Product Research, 2013)

Diversity Assessment of Turkish Maize Landraces Based on Fluorescent Labelled SSR Markers - Gönül Cömertpay; Faheem S. Baloch; Benjamin Kilian; Ahmet C. Ülger; Hakan Özkan (Plant Molecular Biology Reporter, 2012)

Status of Organochlorine Contaminants in the Different Environmental Compartments of Pakistan: A Review on Occurrence and Levels - Syed Ali-Musstjab-Akber-Shah Eqani; Riffat Naseem Malik; Ambreen Alamdar; Hina Faheem (Bulletin of Environmental Contamination and Toxicology, 2012)

Levels of Arsenic, Cadmium, Lead, Manganese and Zinc in Biological Samples of Paralysed Steel Mill Workers with Related to Controls - Hassan Imran Afridi; Tasneem Gul Kazi; Atif G. Kazi; Faheem Shah; Sham Kumar Wadhwa; Nida Fatima Kolachi; Abdul Qadir Shah; Jameel Ahmed Baig; Naveed Kazi (Biological Trace Element Research, 2011)

Evaluation of Toxic Risk Assessment of Arsenic in Male Subjects Through Drinking Water in Southern Sindh Pakistan - Jameel Ahmed Baig; Tasneem Gul Kazi; Abdul Qadir Shah; Hassan Imran Afridi; Sumaira Khan; Nida Fatima Kolachi; Ghulam Abbas Kandhro; Sham Kumar Wadhwa; Faheem Shah (Biological Trace Element Research, 2011)

Erratum: Evaluation of Essential Trace and Toxic Elements in Biological Samples of Normal and Night Blindness Children of Age Groups 3–7 and 8–12 Years - Hassan Imran Afridi; Tasneem Gul Kazi; Naveed Kazi; Ghulam Abbas Kandhro; Jameel Ahmed Baig; Abdul Qadir Shah; Sham Kumar Wadhwa; Sumaira Khan; Nida Fatima Kolachi; Faheem Shah; Mohammad Khan Jamali; Mohammad Balal Arain; et al. (Biological Trace Element Research, 2011)

Erratum: Chromium and Manganese Levels in Biological Samples of Normal and Night Blindness Children of Age Groups (3–7) and (8–12) Years - Hassan Imran Afridi; Tasneem Gul Kazi; Naveed Kazi; Ghulam Abbas Kandhro; Abdul Qadir Shah; Jameel Ahmed Baig; Sham Kumar Wadhwa; Sumaira Khan; Nida Fatima Kolachi; Faheem Shah; Mohammad Khan Jamali; Mohammad Balal Arain (Biological Trace Element Research, 2011)

Status of Toxic Metals in Biological Samples of Diabetic Mothers and Their Neonates - Nida Fatima Kolachi; Tasneem Gul Kazi; Hassan Imran Afridi; Naveed Kazi; Sumaira Khan; Ghulam Abbas Kandhro; Abdul Qadir Shah; Jameel Ahmed Baig; Sham Kumar Wadhwa; Faheem Shah; Mohammad Khan Jamali; Mohammad Balal Arain (Biological Trace Element Research, 2011)

Determination of Arsenic in Scalp Hair of Children and its Correlation with Drinking Water in Exposed Areas of Sindh Pakistan - Tasneem G. Kazi; Jameel A. Baig; Abdul Q. Shah; Muhammad Balal Arain; Muhammad Khan Jamali; Ghulam A. Kandhro; Hassan I. Afridi; Nida F. Kolachi; Sumaira Khan; Sham K. Wadhwa; Faheem Shah (Biological Trace Element Research, 2011)

Distribution of Copper, Iron, and Zinc in Biological Samples (Scalp Hair, Serum, Blood, and Urine) of Pakistani Viral Hepatitis (A–E) Patients and Controls - Nida Fatima Kolachi; Tasneem Gul Kazi; Hassan Imran Afridi; Naveed Kazi; Ghulam Abbas Kandhro; Abdul Qadir Shah; Jameel Ahmed Baig; Sham Kumar Wadhwa; Sumaira Khan; Faheem Shah; Mohammad Khan Jamali; Mohammad Balal Arain (Biological Trace Element Research, 2011)

Chromium and Manganese Levels in Biological Samples of Normal and Night Blindness Children of Age Groups (3–7) and (8–12) Years - Hassan Imran Afridi; Tasneem Gul Kazi; Naveed Kazi; Ghulam Abbas Kandhro; Abdul Qadir Shah; Jameel Ahmed Baig; Sham Kumar Wadhwa; Sumaira Khan; Nida Fatima Kolachi; Faheem Shah; Mohammad Khan Jamali; Mohammad Balal Arain (Biological Trace Element Research, 2011)

Evaluation of Essential Trace and Toxic Elements in Biological Samples of Normal and Night Blindness Children of Age Groups 3–7 and 8–12 Years - Hassan Imran Afridi; Tasneem Gul Kazi; Naveed Kazi; Ghulam Abbas Kandhro; Jameel Ahmed Baig; Abdul Qadir Shah; Sham Kumar Wadhwa; Sumaira Khan; Nida Fatima Kolachi; Faheem Shah; Mohammad Khan Jamali; Mohammad Balal Arain; et al. (Biological Trace Element Research, 2011)

Erratum: Chromium and Manganese Levels in Biological Samples of Pakistani Myocardial Infarction Patients at Different Stages as Related to Controls - Hassan Imran Afridi; Tasneem Gul Kazi; Naveed Kazi; Sirajuddin; Ghulam Abbas Kandhro; Jameel Ahmed Baig; Abdul Qadir Shah; Mohammad Khan Jamali; Mohammad Balal Arain; Sham Kumar Wadhwa; Sumaira Khan; Nida Fatima Kolachi; et al. (Biological Trace Element Research, 2011)

Erratum: Evaluation of Status of Zinc, Copper, and Iron Levels in Biological Samples of Normal Children and Children with Night Blindness with Age Groups of 3–7 and 8–12 Years - Hassan Imran Afridi; Tasneem Gul Kazi; Naveed Kazi; Ghulam Abbas Kandhro; Jameel Ahmed Baig; Abdul Qadir Shah; Sham Kumar Wadhwa; Sumaira Khan; Nida Fatima Kolachi; Faheem Shah; Mohammad Khan Jamali; Mohammad Balal Arain; et al. (Biological Trace Element Research, 2011)

Erratum: Evaluation of Status of Cadmium, Lead, and Nickel Levels in Biological Samples of Normal and Night Blindness Children of Age Groups 3–7 and 8–12 Years - Hassan Imran Afridi; Tasneem Gul Kazi; Naveed Kazi; Sirajuddin; Ghulam Abbas Kandhro; Jameel Ahmed Baig; Abdul Qadir Shah; Sham Kumar Wadhwa; Sumaira Khan; Nida Fatima Kolachi; Faheem Shah; Mohammad Khan Jamali; et al. (Biological Trace Element Research, 2011)

Evaluation of Status of Cadmium, Lead, and Nickel Levels in Biological Samples of Normal and Night Blindness Children of Age Groups 3–7 and 8–12 Years - Hassan Imran Afridi; Tasneem Gul Kazi; Naveed Kazi; Sirajuddin; Ghulam Abbas Kandhro; Jameel Ahmed Baig; Abdul Qadir Shah; Sham Kumar Wadhwa; Sumaira Khan; Nida Fatima Kolachi; Faheem Shah; Mohammad Khan Jamali; et al. (Biological Trace Element Research, 2011)

Evaluation of Status of Zinc, Copper, and Iron Levels in Biological Samples of Normal Children and Children with Night Blindness with Age Groups of 3–7 and 8–12 Years - Hassan Imran Afridi; Tasneem Gul Kazi; Naveed Kazi; Ghulam Abbas Kandhro; Jameel Ahmed Baig; Abdul Qadir Shah; Sham Kumar Wadhwa; Sumaira Khan; Nida Fatima Kolachi; Faheem Shah; Mohammad Khan Jamali; Mohammad Balal Arain; et al. (Biological Trace Element Research, 2011)

Evaluation of Cadmium, Chromium, Nickel, and Zinc in Biological Samples of Psoriasis Patients Living in Pakistani Cement Factory Area - Hassan Imran Afridi; Tasneem Gul Kazi; Naveed Kazi; Ghulam Abbas Kandhro; Jameel Ahmed Baig; Abdul Qadir Shah; Sumaira Khan; Nida Fatima Kolachi; Sham Kumar Wadhwa; Faheem Shah; Mohammad Khan Jamali; Mohammad Balal Arain (Biological Trace Element Research, 2011)

Chromium and Manganese Levels in Biological Samples of Pakistani Myocardial Infarction Patients at Different Stages as Related to Controls - Hassan Imran Afridi; Tasneem Gul Kazi; Naveed Kazi; Sirajuddin; Ghulam Abbas Kandhro; Jameel Ahmed Baig; Abdul Qadir Shah; Mohammad Khan Jamali; Mohammad Balal Arain; Sham Kumar Wadhwa; Sumaira Khan; Nida Fatima Kolachi; et al. (Biological Trace Element Research, 2011)

A molecular evaluation of dengue virus pathogenesis and its latest vaccine strategies - Muhammad Faheem; Ummar Raheel; Muhammad Nasir Riaz; Naghmana Kanwal; Farakh Javed; Najam us Sahar Sadaf Zaidi; Ishtiaq Qadri (Molecular Biology Reports, 2011)

Erratum to: Association of Environmental Toxic Elements in Biological Samples of Myocardial Infarction Patients at Different Stages - Hassan Imran Afridi; Tasneem Gul Kazi; Naveed Kazi; Ghulam Abbas Kandhro; Jameel Ahmed Baig; Mohammad Khan Jamali; Mohammad Balal Arain; Abdul Qadir Shah; Faheem Shah; Sumaira Khan; Nida Fatima Kolachi (Biological Trace Element Research, 2011)

Erratum: Evaluation of Status of Trace and Toxic Metals in Biological Samples (Scalp Hair, Blood, and Urine) of Normal and Anemic Children of Two Age Groups - Faheem Shah; Tasneem Gul Kazi; Hassan Imran Afridi; Naveed Kazi; Jameel Ahmed Baig; Abdul Qadir Shah; Sumaira Khan; Nida Fatima Kolachi; Sham Kumar Wadhwa (Biological Trace Element Research, 2011)

Evaluation of Status of Trace and Toxic Metals in Biological Samples (Scalp Hair, Blood, and Urine) of Normal and Anemic Children of Two Age Groups - Faheem Shah; Tasneem Gul Kazi; Hassan Imran Afridi; Naveed Kazi; Jameel Ahmed Baig; Abdul Qadir Shah; Sumaira Khan; Nida Fatima Kolachi; Sham Kumar Wadhwa (Biological Trace Element Research, 2011)

Association of Environmental Toxic Elements in Biological Samples of Myocardial Infarction Patients at Different Stages - Hassan Imran Afridi; Tasneem Gul Kazi; Naveed Kazi; Ghulam Abbas Kandhro; Jameel Ahmed Baig; Mohammad Khan Jamali; Mohammad Balal Arain; Abdul Qadir Shah; Faheem Shah; Sumaira Khan; Nida Fatima Kolachi (Biological Trace Element Research, 2011)

Nutritional and physicochemical variation in Turkish kabuli chickpea (Cicer arietinum L.) landraces - Sertaç Özer; Tolga Karaköy; Faruk Toklu; Faheem S. Baloch; Benjamin Kilian; Hakan Özkan (Euphytica, 2010)

New phytoconstituents from the stem bark of Tinospora cordifolia Miers - Faheem Ahmad; Mohd. Ali; Prawez Alam (Natural Product Research, 2010)

Testing of rye-specific markers located on 1RS chromosome and distribution of 1AL.RS and 1BL.RS translocations in Turkish wheat (Triticum aestivum L., T. durum Desf.) varieties and landraces - Fulya Eylem Yediay; Faheem Shehzad Baloch; Benjamin Kilian; Hakan Özkan (Genetic Resources and Crop Evolution, 2010)

Amelioration of salinity tolerance in Solanum tuberosum L. by exogenous application of ascorbic acid - Zahoor Ahmad Sajid; Faheem Aftab (In Vitro Cellular & Developmental Biology - Plant, 2009)

Effects of acute tyrosine/phenylalanine depletion on the selective processing of smoking-related cues and the relative value of cigarettes in smokers - Brian Hitsman; James MacKillop; Anne Lingford-Hughes; Tim M. Williams; Faheem Ahmad; Sally Adams; David J. Nutt; Marcus R. Munafò (Psychopharmacology, 2008)

Plant regeneration from protoplasts derived from cell suspension of adventive somatic embryos in sugarcane (Saccharum spp. hybrid cv. CoL-54 and cv. CP-43/33) - Faheem Aftab; Javed Iqbal (Plant Cell, Tissue and Organ Culture (PCTOC), 1999)